Articles You Might Have Missed - Tyler J. Yates; Kathleen Q. Chen; Zackery L. G. Fowler; Haley A. Kelly; Austin W. Gay (Journal of Medical Toxicology, 2026)

Exploring the use of amino acid stable hydrogen isotope ( δ 2 H) analysis to improve geographic assignment of wildlife - Seth D. Newsome; Emma A. Elliott Smith; Christy J. Mancuso; Drew N. Fowler; Keith A. Hobson (Isotopes in Environmental and Health Studies, 2026)

Representation of Long‐Term Observed UK Winter Precipitation Trends and Variability in UKCP18 Global Climate Models - James G. Carruthers; Hayley J. Fowler; Daniel Bannister; Selma B. Guerreiro (International Journal of Climatology, 2026)
Evaluating the representation of observed precipitation trends in historical climate model simulations is challenging due to the combined effects of dynamical and thermodynamic changes and the strong influence of natural variability. Here, we assess the representation of long‐term (1901–2023) trends and variability in UK winter mean precipitation, focusing on the separation of dynamical and non‐dynamical components. We apply a dynamical adjustment methodology to the global climate models (GCMs) of the UK Climate Projections 2018 (UKCP18) to isolate circulation‐driven and non‐dynamical precipitation changes and variability. While several UKCP18 GCMs simulate a winter wetting trend broadly consistent with observations, the underlying drivers differ significantly. Modelled increases are primarily circulation‐driven, whereas observed trends are dominated by thermodynamic forcing. Also, the scaling of precipitation with temperature in ensemble members is substantially weaker than observed. While a thermodynamic signal emerges in the ensemble mean, its magnitude is less than a third of the observed rate. Consequently, these ensemble members may underestimate future non‐dynamical precipitation changes. Furthermore, the ensemble members under‐represent observed dynamical interannual variability, resulting in fewer high‐impact winters associated with persistent large‐scale atmospheric circulation anomalies. These results highlight important limitations in the representation of winter precipitation variability and change in the UKCP18 GCMs and have implications for the interpretation of model output in climate risk assessments and for the use of higher‐resolution ensembles within the UKCP18 framework.

Scaling of Short‐Duration, Summer Rainfall Event Temporal Profiles With Warming Over Great Britain - Alexandra Seawell; Hayley J. Fowler; Stephen Blenkinsop; Caspar J. M. Hewett; Roberto Villalobos Herrera; Marie Hundhausen; Haider Ali (International Journal of Climatology, 2026)
The relationship between extreme rainfall and temperature, known as temperature scaling, is widely used to understand changes in rainfall characteristics under a warming climate. While most previous studies have focussed on fixed‐duration intensities or event totals, this study examines how different aspects of the rainfall temporal profile respond to temperature. Specifically, we focus on temperature scaling of total event depth, maximum sub‐hourly intensity and measures of profile concentration and loading. Using both sub‐hourly rain gauge data across Britain and 10‐min output from a convection‐permitting climate model (CPM) for present and future climates over southern England and Wales, we analyse short‐duration, summer rainstorms. Results show that total rainfall depth increases with temperature, with higher quantiles approaching Clausius‐Clapeyron (CC) scaling rates of 6–7%°C −1 . However, changes are unevenly distributed within the rainfall event temporal structure. Maximum sub‐hourly intensities scale more strongly than total event depth, with upper quantiles reaching 7–11%°C −1 , indicating pronounced intensification of short‐duration rainfall extremes at high temperatures. Accumulation of 50% of the rainfall event volume was found to occur over a shorter fraction of the storm duration and earlier in the storm duration, indicating rainfall events are more concentrated and more front‐loaded at higher temperatures, with both scaling at rates of 1–2%°C −1 . These results suggest that future summer rainstorms will not only deliver greater overall rainfall in a warming climate, but also produce more intense and earlier bursts of precipitation, heightening flash flood risk. Disregarding these temporal shifts may lead to underestimation of flood hazards and misrepresentation of climate change impacts in hydrological modelling and infrastructure design.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Estimation of root zone water storage capacity (Sr) in natural ecosystems subject to high interannual climate variability - Maryam Khorami; Gary J. Sheridan; Keirnan Fowler; Patrick N.J. Lane (Journal of Hydrology, 2026)

Amplification of ENSO’s influence on the atmospheric circulation over Western Tibetan Plateau in autumn during 1948–2021 - Yangjie Jiang; Xiao-Feng Li; Xin Zhou; Hayley J. Fowler; Song Yang (Global and Planetary Change, 2026)

Low foliar nitrogen and elevated defensive metabolites in the invasive weed Calluna vulgaris (heather) may impair biocontrol agent performance - D. Paul Barrett; Maria A. Minor; Paul Peterson; Simon V. Fowler; Arvind K. Subbaraj; David J. Lun; Andrea Clavijo McCormick (Biological Invasions, 2026)
Introducing insect biocontrol agents to manage invasive plants is an effective and sustainable management option. However, biocontrol agents sometimes fail to establish or are ineffective in the new range. Heather beetle Lochmaea suturalis, (Thomson, 1866) (Coleoptera: Chrysomelidae) sourced from the United Kingdom (UK), was introduced into New Zealand’s North Island Central Plateau (CP) to control invasive Calluna vulgaris (L.) Hull (heather). The beetle was difficult to establish and the few populations that did, achieved poor population growth rates and expansion in contrast to the rapid rates associated with its conspecifics in the UK. We hypothesize that low soil nutrients such as nitrogen and phosphorous (N and P) on the CP may be linked to changes in C. vulgaris’ primary nutritional and secondary defensive metabolites, leading to poor beetle performance. Testing this hypothesis involved application of N and P to soil in C. vulgaris field plots, measurement of foliar N and Carbon (C), plus using non-targeted metabolomics, exploring differences in the primary and secondary metabolites between treatments. Raising soil nutrients amplified several primary metabolites including N-based amino acids and concomitantly reduced the majority of phenylpropanoids, a secondary metabolite group containing many defensive compounds. This work seeks to better understand, how abiotic conditions in a new environment, influence invasive plant metabolism, potentially altering the efficiency of foliage assimilation which may impair biocontrol agent establishment and effectiveness. Such understanding may be applied to mitigate potential foliar deficiencies at release sites and contribute to improving success rates of biocontrol as a management strategy for invasive plants.

Environmental Gradients Decouple Demographic and Adaptive Connectivity in a Highly Mobile Coastal Marine Species - Chris J. Brauer; Andrea Bertram; Jonathan Sandoval‐Castillo; Anthony Fowler; Justin D. Bell; Paul Hamer; Maren Wellenreuther; Luciano B. Beheregaray (Molecular Ecology, 2026)
Understanding how eco‐evolutionary processes shape genetic variation and persistence in marine species with highly variable recruitment dynamics and dispersal potential remains a fundamental challenge, particularly when considering the interplay between gene flow and local adaptation. Here, we employed a seascape genomics approach to investigate population connectivity and local adaptation in Australasian snapper ( Chrysophrys auratus , Sparidae) along 1500 km of the environmentally heterogeneous southern Australian coastline. Using genome‐wide SNPs, we identified distinct eastern and western regional populations aligned with known biogeographical regions. Genotype‐environment association analyses revealed 855 candidate adaptive loci associated with environmental variation, including temperature, salinity and primary productivity. Connectivity analyses using neutral markers indicated high gene flow within both eastern and western regions, while candidate adaptive loci revealed substantially reduced connectivity, especially for Northern Spencer Gulf and West Coast populations. This contrast implies a decoupling of demographic and adaptive connectivity, in which strong environmental gradients appear to reduce the effective exchange of adaptive variation despite high overall connectivity. Our results support contingent migration as a potential mechanism modulating the balance between local adaptation and gene flow in this economically and ecologically important marine species. These findings might also have implications for regional management of other coastal fisheries that are experiencing substantial declines. As climate change alters coastal marine environments around the world, the dynamics of local recruitment, site fidelity and local adaptation are expected to change. This highlights the importance of integrating knowledge about eco‐evolutionary processes into marine resource management, fisheries stock assessment, and restocking and stock enhancement activities.

Suitability of the use of the intraperitoneal route in the in vivo micronucleus test to evaluate the genotoxicity of hair dyes - Nicola J. Hewitt; Hind Assaf Vandecasteele; Paul Benndorf; Rolf Fautz; Anne Fuchs; Karma Fussell; Carsten Goebel; Torben König; Fabrice Nesslany; Juliane Werner; Paul Fowler (Regulatory Toxicology and Pharmacology, 2026)

Evaluation of reanalyzed surface air temperature over the western Tibetan Plateau - Jing Wang; Xiao-Feng Li; Jingzhi Wang; Xin Lai; Song Yang; Nathan Forsythe; Hayley J. Fowler (Atmospheric Research, 2026)

Linking Climate and Demography to Predict Population Dynamics and Persistence Under Global Change - Jennifer L. Williams; Amy L. Angert; Aldo Compagnoni; Ali Campbell; Megan L. DeMarche; Margaret E. K. Evans; Joshua C. Fowler; Edgar J. González; Amy M. Iler; Jenna A. Loesberg; Allison M. Louthan; Alexandra B. Martin; et al. (Ecology Letters, 2025)
Predicting the effects of climate change on plant and animal populations is an urgent challenge for understanding the fate of biodiversity under global change. At the surface, quantifying how climate drives the vital rates that underlie population dynamics appears simple, yet many decisions are required to connect climate to demographic data. Competing approaches have emerged in the literature with little consensus around best practices. Here we provide a practical guide for how to best link vital rates to climate for the purposes of inference and projection of population dynamics. We first describe the sources of demographic and climate data underlying population models. We then focus on best practices to model the relationships between vital rates and climate, highlighting what we can learn from mechanistic and phenomenological models. Finally, we discuss the challenges of prediction and forecasting in the face of uncertainty about climate‐demographic relationships as well as future climate. We conclude by suggesting ways forward to build this field of research into one that makes robust forecasts of population persistence, with opportunities for synthesis across species.

Longitudinal transitions in sedentary behavior and physical activity in relation to all-cause and cause-specific mortality among postmenopausal women - Zhong-Yue Liu; Guo-Chong Chen; Michael J. LaMonte; Victor Kamensky; Kelly R. Evenson; Aladdin H. Shadyab; Juhua Luo; Matthew Allison; Robert A. Wild; Scott B. Going; Charles B. Eaton; Katie L. Stone; et al. (GeroScience, 2025)

Trade regulations drive improved global shark and ray management - Mark E. Bond; Hollie Booth; Akshay Tanna; Sarah L. Fowler; Carlos J. Polo-Silva; K.H. Stanley Shea; Floriane Cardiec; Elisabeth F. Mansur; Rima W. Jabado (Marine Policy, 2025)

A synoptic view of the Western Tibetan Vortex - Binbo Lei; Xiao-Feng Li; Yanjie Li; Song Yang; Hayley J. Fowler; Nathan Forsythe (Atmospheric Research, 2025)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Patterns and drivers of movement in the estuary-associated sparid Acanthopagrus australis from a large-scale tagging study - Holly Gunton; Ashley M. Fowler; David J. Booth; John Stewart (Fisheries Research, 2025)

High-resolution climate models improve simulation of monsoon rainfall changes in the Ganga–Brahmaputra-Meghna basin - Haider Ali; Hayley J. Fowler; Andrew G. Turner (Climate Dynamics, 2025)
This study investigates the impact of model resolution on simulating South Asian monsoon rainfall, focusing on the Ganges–Brahmaputra-Meghna (GBM) basin. By comparing high- and low-resolution versions of four CMIP6 HighResMIP model families against reference datasets (MSWEP and ERA5), we emphasize the advantages of high-resolution models in accurately simulating key monsoon characteristics, including annual rainfall, timing, intensity, and duration. Our results show that the high-resolution models align more closely with observed data, outperforming their low-resolution counterparts. Between 1979 and 2014, the high-resolution model ensemble (HR-models) captures key shifts in monsoon timing, such as delayed onset and withdrawal, leading to a slight increase in monsoon duration. In contrast, the low-resolution ensemble (LR-models) showed more pronounced delays in onset. The observational datasets, MSWEP and ERA5, indicate earlier (7 ± 3 days) and later (3 ± 1.2 days) onsets, respectively, with both showing delays in withdrawal, indicating extended monsoon duration. Notably, the increase in monsoon duration is more pronounced in MSWEP observations than in the model simulations, particularly for LR-models. Regarding rainfall trends, the HR-models more accurately reflect observed changes in both total rainfall and extreme rainfall from 1979–2014 compared to LR-models. Future projections (2015–2050) indicate further delays in monsoon onset, with HR-models projecting larger increases in total rainfall and extreme events (up to 4.5%/decade for the 95th percentile of rainfall) compared to LR-models, which show smaller increases and higher variability in total and extreme rainfall. These findings highlight the critical role of model resolution in improving the accuracy of monsoon simulations, with HR models offering more reliable simulations of historical monsoon behaviour and therefore likely more robust projections of future monsoon behavior. These are essential for informed water management and agricultural decision-making over the complex topography of the GBM basin.

A climatology of local hourly wet spells across the tropics - Vincent Moron; Erwan Cornillault; Haider Ali; Hayley J. Fowler; Andrew W. Robertson (Climate Dynamics, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Variable post-capture condition estimated by visual assessment for key recreational species discarded in a nearshore marine charter fishery off eastern Australia - Julian M. Hughes; Daniel D. Johnson; Faith A. Ochwada-Doyle; Jeffrey J. Murphy; Matthew D. Taylor; Ashley M. Fowler (Fisheries Research, 2025)

Differential survival of Ilyanassa obsoleta to water temperature and association with the non-native red alga Gracilaria vermiculophylla - Timothy S. Lee; Amy E. Fowler; Jessica R. Largen; Jonathan P. Russo; Zackary J. Schlegel; Dawson K. Wright; April M. H. Blakeslee (Hydrobiologia, 2025)
Along the U.S. east coast, the widespread non-native red alga Gracilaria vermiculophylla provides habitat for an array of macroinvertebrates, including the eastern mudsnail Ilyanassa obsoleta . Though I. obsoleta tolerates a wide temperature range, increases in summer water temperatures may enhance mortality; furthermore, the presence of non-native algae in rising seawater temperatures could exacerbate harmful conditions. We tested how the presence or absence of G. vermiculophylla influenced snail mortality across a range of summer temperatures over a 3-week period. We found that I. obsoleta survived the longest in the lowest temperature (27 °C), followed by the medium (32 °C), and lastly the highest (36 °C) where all snails died within 2 days. Mortality was also higher and faster for snails in the presence versus absence of G. vermiculophylla . We suspected dissolved oxygen became very low at the higher temperatures with G. vermiculophylla ; thus we conducted a laboratory-based dissolved oxygen experiment. We found that G. vermiculophylla degraded and oxygen declined faster at the highest temperature treatment, thereby creating anoxic conditions. Altogether, our results demonstrate that G. vermiculophylla could enhance anoxic conditions at high summer temperatures, potentially leading to enhanced faunal mortality.

Early life history traits and elevated growth trajectories associated with survival into winter in range-expanding coral reef fish - Alexander L. Rigg; Ashley M. Fowler; Brigitte Sommer; David J. Booth (Marine Biology, 2025)
Climate change is driving the poleward range expansion of sub-tropical and tropical marine species into temperate ecosystems, with ocean-warming hotspots experiencing rapid shifts in species distributions. While recruitment to temperate waters by expatriating tropical vagrant fish is increasing, surviving through the cooler winters remains a significant barrier to their establishment. This study investigates the links between early life history traits and survival into winter in the Sergeant Major ( Abudefduf vaigiensis ), a tropical damselfish expanding its range into temperate southeastern Australia. Using otolith microstructure analysis, we reconstructed the early life histories of 122 individuals collected from rocky reefs in Sydney (33.8 o S) Australia in 2022 and 2023 and assessed their early life history traits. Our results demonstrate that individuals sampled during winter (hereafter “wintered fish”) had a larger size at hatching, longer pelagic larval duration, and higher body condition than fish collected before winter. Lower settlement water temperatures were positively associated with winter survival, indicating that a settlement date closer to the onset of winter was favourable. Additionally, wintered fish, exhibited higher growth rates in early life compared to fish sampled prior to winter onset. These findings suggest that some early life history traits are selected for survival into winter, potentially mediating the physiological impacts of declining water temperature. If such traits increase overwinter survival they may facilitate the establishment of this range-expanding species in temperate rocky reef environments.

Global assessment of manta and devil ray gill plate and meat trade: conservation implications and opportunities - Marta D. Palacios; Laura Weiand; Betty J. L. Laglbauer; Melissa R. Cronin; Sarah Fowler; Rima W. Jabado; Thanda Ko Gyi; Daniel Fernando; Godefroy De Bruyne; Stanley K. H. Shea; Paul Hilton; Yi-Li Gao; et al. (Environmental Biology of Fishes, 2025)

Faster larval growth and shorter pelagic duration enhance the post-settlement persistence of a common range-extending coral-reef fish in a temperate ecosystem - Alexander L. Rigg; Ashley M. Fowler; Ivan Nagelkerken; David J. Booth (Coral Reefs, 2025)
Climate-induced ocean warming facilitates the poleward range expansion of tropical marine species into temperate waters. Such tropicalisation is reshaping marine ecosystems globally and has ecological implications. Our understanding of the factors influencing the establishment and persistence of vagrant tropical species in temperate waters remains limited. To address this knowledge gap, we examined which early life history traits affect the post-settlement persistence of a vagrant tropical fish, the sergeant major damselfish Abudefduf vaigiensis , in temperate waters off southeast Australia. Over an 8-week period, fish were collected, and otolith microstructure analysis indicated that early post-settlement persistence was linked to fast larval growth in the week prior to settlement and to shorter pelagic larval duration, but not body size at hatching or body size at settlement. We conclude that successful invasions of temperate ecosystems by this vagrant tropical fish is likely mediated by demographic advantages these fish gain as early-stage larvae.

Overwintering performance of three juvenile temperate estuarine fishes - Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Experimental Marine Biology and Ecology, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

A multi-objective optimization model for cropland design considering profit, biodiversity, and ecosystem services - Caleb H. Geissler; Nathan L. Haan; Bruno Basso; Ames Fowler; Douglas A. Landis; Tyler J. Lark; Christos T. Maravelias (Ecological Modelling, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Effects of season, size, and sex on tolerance of a simulated cold snap in latitudinally separated populations of the poleward-invading green porcelain crab (Petrolisthes armatus) - Kevin J. Mack; Dara H. Wilber; Amy E. Fowler; Robert D. Podolsky (Journal of Experimental Marine Biology and Ecology, 2024)

Atmospheric patterns associated with summer sub-daily rainfall extremes in western Europe - Anna C. Whitford; Stephen Blenkinsop; Hayley J. Fowler (Climate Dynamics, 2024)
Large-scale atmospheric circulations are a significant driver of rainfall extremes. However, little attention has so far been devoted to understanding how large-scale circulation patterns influence sub-daily rainfall extremes. Using a gauge-based sub-daily rainfall dataset, we investigate the relationship between large-scale circulations and 3-hour extremes (defined here as ≥ 40 mm rainfall in 3 h) for western Europe. A set of 30 weather patterns (WPs) developed by the UK Met Office and reanalysis data of geopotential height at 500 hPa (z500) are used to represent large-scale atmospheric conditions. Strong associations with 3-hour extremes are found for a small number of WPs: over 50% of 3-hour rainfall extremes across Western Europe occur with just 5 WPs. Composites of z500 reveal the WPs resulting in southerly or south-westerly flow along the leading edge of a trough, accompanied by a ridge to the east or northeast, are most favourable for sub-daily rainfall extremes, with a statistically significant difference between the atmospheric conditions on WP days with a 3-hour extreme rainfall event compared to WP non-event days. Given that large-scale circulations are predictable much further in advance than individual extreme rainfall events, these identified relationships could therefore have important implications for forecasting, aiding in the early identification of periods with increased risk of short-duration rainfall extremes.

A simple and robust approach for adapting design storms to assess climate-induced changes in flash flood hazard - Nadav Peleg; Daniel B. Wright; Hayley J. Fowler; João P. Leitão; Ashish Sharma; Francesco Marra (Advances in Water Resources, 2024)

Two applications of the Consensus Solutions process with collaborative modeling for management of a contentious oyster fishery - Elizabeth W. North; Michael J. Wilberg; Jeff Blair; Lisa Wainger; Jeffrey C. Cornwell; Robert Jones; Chris Hayes; Rasika Gawde; Raleigh Robert Hood; Taylor Goelz; Troy Hartley; Marvin M. Mace; et al. (Frontiers in Marine Science, 2024)
Worldwide, enhancement of oyster populations is undertaken to achieve a variety of goals including support of food production, local economies, water quality, coastal habitat, biodiversity, and cultural heritage. Although numerous strategies for improving oyster stocks exist, enhancement efforts can be thwarted by long-standing conflict among community groups about which strategies to implement, where efforts should be focused, and how much funding should be allocated to each strategy. The objective of this paper is to compare two engagement approaches that resulted in recommendations for multi-benefit enhancements to oyster populations and the oyster industry in Maryland, U.S.A., using the Consensus Solutions process with collaborative simulation modeling. These recommendations were put forward by the OysterFutures Workgroup in 2018 and the Maryland Oyster Advisory Commission (OAC) in 2021. Notable similarities between the efforts were the basic principles of the Consensus Solutions process: neutral facilitation, a 75% agreement threshold, the presence of management agency leadership at the meetings, a scientific support team that created a management scenario model in collaboration with community group representatives, numerous opportunities for representatives to listen to each other, and a structured consensus building process for idea generation, rating, and approval of management options. To ensure meaningful representation by the most affected user groups, the goal for membership composition was 60% from industry and 40% from advocacy, agency, and academic groups in both processes. Important differences between the processes included the impetus for the process (a research program versus a legislatively-mandated process), the size of the groups, the structure of the meetings, and the clear and pervasive impact of the COVID-19 pandemic on the ability of OAC members to interact. Despite differences and challenges, both groups were able to agree on a package of recommendations, indicating that consensus-based processes with collaborative modeling offer viable paths toward coordinated cross-sector natural resource decisions with scientific basis and community support. In addition, collaborative modeling resulted in ‘myth busting’ findings that allowed participants to reassess and realign their thinking about how the coupled human-oyster system would respond to management changes.

Tree of life metabarcoding can serve as a biotic benchmark for shifting baselines in urbanized estuaries - Joseph D. DiBattista; Ashley M. Fowler; Tanika C. Shalders; Robert J. Williams; Shaun Wilkinson (Environmental Research, 2024)

Individual performance niches and responses to winter temperature change in three estuarine fishes from eastern Australia - Clara Bellotto; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
Climate change may impact individual organisms in different ways, a consideration often overshadowed by predominant focus on population effects in studies. We examined three estuarine fish species to determine if individual fish performance, persisted across winter water temperatures. Fish performance at 16 °C (current Sydney winter estuarine water temperature) and 20 °C (predicted under climate change) with low and high food regimes was assessed using key physiological (growth, aerobic scope, burst speed) and behavioural parameters (foraging activity, boldness, shelter usage, predator escape response). We expected a strong positive relationship between performance at 16 °C and 20 °C for each parameter, and interactions with food level, however in general this was not found for any species. Relative performance was only maintained across temperatures for a few parameters, such as bite rate, boldness, and shelter response in one species (trumpeter Pelates sexlineatu s), with aerobic scope in silver biddy Gerres subfasciatus , and boldness in fortescue Centropogon australis . Our results suggest that individuals’ fitness (directly via changes in growth, indirectly via behaviours) might be impacted by climate warming due to differences in relative performance among juvenile individuals across water temperatures. Changes in relative performance among individuals may initially compensate for a population-level response, thereby buffering the effects of climate change.

How uncertain and observable are marine ecosystem indicators in shelf seas? - Jozef Skákala; David Ford; Alison Fowler; Dan Lea; Matthew J. Martin; Stefano Ciavatta (Progress in Oceanography, 2024)

Climatology of severe hail potential in Europe based on a convection-permitting simulation - Abdullah Kahraman; Elizabeth J. Kendon; Hayley J. Fowler (Climate Dynamics, 2024)
We present a new approach to identify severe hailstorms in a convection-permitting climate model, and build a climatology of severe hail potential in Europe using an ingredients-based approach based on a 20-year long hindcast simulation. Severe hail in Europe occurs mostly in southern regions (up to 40 times a year per 10,000 km 2 around Northern Italy), and from May to August. It peaks from afternoon to evening hours on land, whilst sea areas are prone to hail at any time of the day. The Mediterranean Sea experiences severe hailstorms mostly in autumn: the central Mediterranean has the highest frequency among all regions studied, and may be considered as an unknown alley for hailstorms in Europe. Results derived from the high-resolution model are in very good agreement with existing hail climatologies constructed from observations, including the fine scale spatial variation. We conclude that our approach provides a reliable proxy for studying future changes in severe hail in convection-permitting simulations.

Mineral–water reactions in Earth’s mantle: Predictions from Born theory and ab initio molecular dynamics - Sarah J. Fowler; David M. Sherman; John P. Brodholt; Oliver T. Lord (Geochimica et Cosmochimica Acta, 2024)

Predator-avoidance behaviour of target and non-target temperate reef fishes is lower in areas protected from fishing - David A. Feary; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
The effects of hunting on predator-avoidance behaviour are increasingly being recognised on land but have received less attention in marine systems. We examined whether predator-avoidance behaviour of temperate reef fishes differed between areas protected and not protected from recreational fishing by examining the flight-initiation distance (FID; the distance a predator can approach before the prey animal flees) of six common species in southeastern Australia. By testing species that ranged in desirability to recreational fishers, we could determine if behavioural differences were specific to target species or extended more broadly throughout the assemblage. After accounting for potential variability among sites within protection levels, we found that the FID of all species was higher in fished areas than protected areas, with FID up to 2.4 times higher in fished areas. The two commonly targeted species had the greatest FID response to fishing. FID also increased with body size for all but one species. Our findings indicate the potential for assemblage-wide effects of fishing on predator-avoidance behaviour and are consistent with an indirect mechanism of behavioural modification.

Staining protocols affect use of otolith to estimate the demography of the damselfish sergeant major ( Abudefduf vaigiensis ) - Alexander L. Rigg; Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Fish Biology, 2024)
This study assessed the otolith (sagittae, lapilli, and asterisci) increment deposition rate in the range‐shifting damselfish, A. vaigiensis , using different concentrations of Alizain Red S and evaluated the impact of staining on increment width. Daily increment deposition was verified in all otolith types and presented clearer fluorescent markings in the lapilli and sagittae than the asterisci, with high stain concentration showing the best clarity. Higher stain concentrations were found to decrease increment width, suggesting care is needed when using stained otoliths as a proxy for growth for this species.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

ENSO and IOD contributions to seasonal meteorological droughts over the Yangtze River basin - Hao Yin; Hayley J. Fowler; Stephen Blenkinsop; Zhiyong Wu; Hai He; Yuan Li (International Journal of Climatology, 2023)
The Yangtze River basin (YRB) has experienced frequent extreme drought events in recent years. Many studies have explored the impact of anomalous tropical sea surface temperatures on seasonal meteorological droughts over the YRB, yet two critical issues remain: (1) the regimes of the El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) causing YRB droughts; (2) the timing and spatial pattern of YRB droughts caused by ENSO and IOD. To address these knowledge gaps, we employed a comprehensive investigation. First, the Severity–Area–Density (SAD) method is applied to identify seasonal drought events over the YRB during 1971–2022. Second, we utilize composite analysis to specify the effects of ENSO and IOD. Our findings indicate that YRB droughts are significantly increased in the August of combined Eastern Pacific (EP) El Niño and positive IOD developing years, October of Central Pacific (CP) El Niño developing years, January of EP La Niña years, and April of CP El Niño decaying years. Third, we conduct numerical simulations and conclude that ENSO and IOD events contribute to the YRB droughts by modulating large‐scale circulation patterns, triggering the formation of cyclones and anticyclones over the Western North Pacific (WNP) and the Tibetan Plateau, and affecting the westerlies and other water vapour transport processes. These results on the physical mechanisms causing seasonal drought in the YRB can guide drought monitoring and prediction in the region.

Subtropical coral expansion into SE Australia: a haven for both temperate and expatriating tropical reef fishes - Max J. O’Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Coral Reefs, 2023)
We examined reef fish assemblages in and adjacent to a newly established coral bed (subtropical Pocillopora aliciae ) in temperate south-eastern Australia, to understand whether novel coral habitat is facilitating assemblages of range-expanding tropical and local temperate fishes. This is the first comprehensive assessment of fish species associating with this novel coral habitat within a temperate environment. Twenty fish species were observed associating with the coral (8 tropical and 12 temperate). Both temperate and tropical species were observed at greater (up to 48 times higher) densities on the coral than on nearby temperate rocky reef in the area, suggesting that the corals generally concentrate fish and may aid in tropicalisation for species that use subtropical coral as habitat. Future research should investigate the ongoing expansion of this coral, the relative quality of coral habitat for fish in temperate regions and the potential implications for functioning of temperate rocky reef ecosystems.

The creation and climatology of a large independent rainfall event database for Great Britain - Roberto Villalobos Herrera; Stephen Blenkinsop; Selma B. Guerreiro; Hayley J. Fowler (International Journal of Climatology, 2023)
Extreme rainfall studies generally focus on hourly or daily rainfall accumulations. Additionally, studies focus on annual maxima (AM) or ‘peak intensities’. Although this approach is useful, the use of fixed‐duration accumulations simplifies inherently continuous rainfall processes which, at a rain gauge, are experienced as rainstorms of varying duration. A gap also exists in the study of sub‐hourly rainfall extremes which are an important source of flash floods. Here, we present the first large‐scale study of rainstorms in the United Kingdom. We leverage a recently created sub‐hourly resolution rain gauge dataset for Great Britain to identify over 70,000 rainstorms that generated AM rainfall intensities across a range of sub‐hourly to daily durations at 1279 rain gauges up to 2018. Our findings are consistent with previous studies of UK rainfall extremes and their climatology, where strong east–west differences are found in the magnitude of autumn and winter long‐duration (over 12‐h) rainstorms. We observe broad similarities in the behaviour of short (under 4‐h) rainstorms across GB, which are dominated by seasonal variations in convective activity rather than by geographical location. Our study reveals substantial overlaps between AM of different durations, with single rainstorms containing AM across a wide range of durations. We also demonstrate the substantial correlation between rainstorm duration and volume. These results challenge common independence assumptions used in the statistical modelling of rainfall extremes using extreme value theory. Our results represent an opportunity to refine rainfall design methods towards improved, robust representations of rainstorms.

Synergistic benefits of recovered carbon black demineralisation for tyre recycling - Alex J Bowles; Amy L Wilson; Geoffrey D Fowler (Resources, Conservation and Recycling, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Phylogenomics reveals extreme gene tree discordance in a lineage of dominant trees: hybridization, introgression, and incomplete lineage sorting blur deep evolutionary relationships despite clear species groupings in Eucalyptus subgenus Eudesmia - Todd G.B. McLay; Rachael M. Fowler; Patrick S. Fahey; Daniel J. Murphy; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Molecular Phylogenetics and Evolution, 2023)

Basin-scale riverine ecosystem services vary with network geometry - Seema Karki; J Angus Webb; Michael J. Stewardson; Keirnan Fowler; Giri Raj Kattel (Ecosystem Services, 2023)

Forces, electric fields and currents at the subsolar martian MPB: MAVEN observations and multifluid MHD simulation - G. Boscoboinik; C. Bertucci; D. Gomez; C. Dong; L. Regoli; C. Mazelle; J. Halekas; J. Espley; C.M. Fowler; D. Mitchell; L. Andersson (Icarus, 2023)

The utility of otolith-based methods for discriminating stock structure of the fishery important monacanthid, Nelusetta ayraud, over an intermediate scale - Holly Gunton; Ashley M. Fowler; Marcus E. Miller; David J. Booth; John Stewart (Fisheries Research, 2023)

Relation between storm characteristics and extreme precipitation statistics over CONUS - Diogo S.A. Araujo; Francesco Marra; Haider Ali; Hayley J. Fowler; Efthymios I. Nikolopoulos (Advances in Water Resources, 2023)

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Drivers and barriers to participation in Sweden's local flexibility markets for electricity - J. Palm; A.-R. Kojonsaari; I. Öhrlund; N. Fowler; C. Bartusch (Utilities Policy, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

The time of emergence of climate-induced hydrologic change in Australian rivers - Andrew John; Rory Nathan; Avril Horne; Keirnan Fowler; Michael Stewardson; Murray Peel; J. Angus Webb (Journal of Hydrology, 2023)

Conservation of endangered galaxiid fishes in the Falkland Islands requires urgent action on invasive brown trout - J. F. Minett; D. M. Fowler; J. A. H. Jones; P. Brickle; G. T. Crossin; S. Consuegra; C. Garcia de Leaniz (Biological Invasions, 2023)
Non-native salmonids are protected in the Southern hemisphere where they sustain aquaculture and lucrative sport fisheries, but also impact many native fishes, which poses a conservation conundrum. Legal protection and human-assisted secondary releases may have helped salmonids to spread, but this has seldom been tested. We reconstructed the introduction of brown trout ( Salmo trutta ) to the Falkland Islands using historical records and modelled its dispersal and probability of invasion using a generalized linear model and Leave One out Cross Validation. Our results indicate that establishment success was ~ 88%, and that dispersal was facilitated over land by proximity to invaded sites and density of stream-road crossings, suggesting it was human assisted. Brown trout have already invaded 54% of Falkland rivers, which are 2.9–4.5 times less likely to contain native galaxiids than uninvaded streams. Without strong containment we predict brown trout will invade nearly all suitable freshwater habitats in the Falklands within the next ~ 70 years, which might put native freshwater fishes at a high risk of extinction.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The FishPath approach for fisheries management in a data‐ and capacity‐limited world - Natalie A. Dowling; Jono R. Wilson; Jason M. Cope; Dawn T. Dougherty; Serena Lomonico; Carmen Revenga; Brian J. Snouffer; Natalio Godoy Salinas; Felipe Torres‐Cañete; Rowan C. Chick; Ashley M. Fowler; Ana M. Parma (Fish and Fisheries, 2023)
Successful fisheries management systems tend to be underpinned by harvest strategies, specifying formally agreed data collection systems, assessment approaches and management measures used to regulate fishing pressure. While harvest strategies can be effective even in data‐ and capacity‐limited (DCL) situations, their development remains challenging in such contexts. We present a process and decision‐support tool, FishPath, to guide the identification of suitable harvest strategy component options given often debilitating conditions: (i) resource limitations and lack of technical management capacity; (ii) ‘uniqueness’ of DCL fisheries; (iii) the concept of harvest strategies is unfamiliar to managers and scientists, and the universe of options is hard to navigate; and (iv) the lack of an effective participatory process to identify solutions tailored to local contexts. These conditions can lead to either management paralysis or generic solutions that may be poor fits to specific conditions. The FishPath Tool uses a diagnostic questionnaire that elicits the key characteristics and specific circumstances of a fishery. It compares these with the requirements of alternative options from an inventory of possible harvest strategy components, identifies where these requirements are met and provides customised, transparent guidance on the appropriateness of component options of a harvest strategy, specific to the fishery of interest and its governance context. The FishPath Process is a facilitated multi‐stakeholder, participatory engagement process aimed to set fisheries on the path to develop a harvest strategy. The FishPath Process and Tool combine to ensure a bottom‐up, documented, transparent, replicable and efficient process.

Leading modes of wind field variability over the western Tibet Plateau - Jingzhi Wang; Xiao-Feng Li; Shaofeng Liu; Ting Liu; Yongjiu Dai; Song Yang; Hayley J. Fowler (Climate Dynamics, 2023)
Atmospheric circulations bring moisture from above the ocean to the high mountains of the western Tibet Plateau (TP), thus wind variability is of great importance to the water cycle centered on the western TP. This study therefore examines the leading modes of the wind fields over the western TP. We use the multivariate empirical orthogonal function (MV-EOF) analysis method to detect the dominant wind patterns above the western TP. This method extracts the leading modes of combined meridional and zonal wind variability at 200-hPa in the region of 22° N–50° N, 50° E–92° E. We find the first leading mode of the combined zonal and meridional wind field in the annual mean and in most seasons (spring, summer and autumn) over the western TP shows high similarity to the Western Tibetan Vortex (WTV), a large-scale atmospheric vortex-like pattern recently recognized over the western TP. In winter, the WTV, however, is closer to the second leading mode. We estimate the sensitivity of our results by changing the domain of the MV-EOF analysis region surrounding the western. We find the influence of the WTV is less sensitive to analysis location around the western TP. In short, the WTV generally represents the first leading mode of the wind field in most seasons over the western TP. This study augments our knowledge on wind variability over the western TP.

Temporally compounding heatwave–heavy rainfall events in Australia - Christoph Sauter; Christopher J. White; Hayley J. Fowler; Seth Westra (International Journal of Climatology, 2023)
Natural hazards often occur in combination with other natural hazards rather than as isolated events. While some combinations of hazards are well studied and their physical connection is increasingly understood, other combinations have received considerably less attention. High temperatures are known to be an important component for conditions that lead to heavy rainfall; however, sequences of heatwaves followed by heavy rainfall are not well understood, especially in a compound event context. Here, we analyse heatwave–heavy rainfall events across Australia using rainfall observations at hourly resolution. Our results show that heavy rainfall is more likely to occur if preceded by a heatwave, demonstrating that heatwave–heavy rainfall sequences should be seen as temporally compounding events. In particular, many regions in Australia experience both more frequent and more extreme wet days immediately following a heatwave. This behaviour is strongest in coastal regions, especially on the Australian east coast. These findings highlight the need for heatwave–heavy rainfall sequences to be studied as compounding events, as future changes in either hazard is likely to have impacts on related risks such as flash flooding.

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Putting sharks on the map: A global standard for improving shark area-based conservation - Ciaran A. Hyde; Giuseppe Notarbartolo di Sciara; Lynn Sorrentino; Charlotte Boyd; Brittany Finucci; Sarah L. Fowler; Peter M. Kyne; Guido Leurs; Colin A. Simpfendorfer; Michael J. Tetley; Freya Womersley; Rima W. Jabado (Frontiers in Marine Science, 2022)
Area-based conservation is essential to safeguard declining biodiversity. Several approaches have been developed for identifying networks of globally important areas based on the delineation of sites or seascapes of importance for various elements of biodiversity (e.g., birds, marine mammals). Sharks, rays, and chimaeras are facing a biodiversity crisis with an estimated 37% of species threatened with extinction driven by overfishing. Yet spatial planning tools often fail to consider the habitat needs critical for their survival. The Important Shark and Ray Area (ISRA) approach is proposed as a response to the dire global status of sharks, rays, and chimaeras. A set of four globally standardized scientific criteria, with seven sub-criteria, was developed based on input collated during four shark, biodiversity, and policy expert workshops conducted in 2022. The ISRA Criteria provide a framework to identify discrete, three-dimensional portions of habitat important for one or more shark, ray, or chimaera species, that have the potential to be delineated and managed for conservation. The ISRA Criteria can be applied to all environments where sharks occur (marine, estuarine, and freshwater) and consider the diversity of species, their complex behaviors and ecology, and biological needs. The identification of ISRAs will guide the development, design, and application of area-based conservation initiatives for sharks, rays, and chimaeras, and contribute to their recovery.

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recruiting a long way from home: Domino damselfish Dascyllus trimaculatus can detect new temperate coral habitat and conspecifics - Max J. O'Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Journal of Fish Biology, 2022)
Climate change is driving tropicalisation of temperate reefs, yet it is unclear how range‐shifting tropical fishes locate suitable habitat. The authors tested whether juvenile tropical damsels Dascyllus trimaculatus could detect rare coral habitat ( Pocillopora aliciae ) and conspecifics on temperate rocky reefs using olfactory and visual preference experiments. For all cues, individuals selected and spent more time than expected in aquarium areas with the cue present, which included coral odour and conspecific odour and visual cues. This indicates that vagrant coral‐reef fish can detect rare suitable habitat outside of their natal range.

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Extreme windstorms and sting jets in convection-permitting climate simulations over Europe - Colin Manning; Elizabeth J. Kendon; Hayley J. Fowler; Nigel M. Roberts; Ségolène Berthou; Dan Suri; Malcolm J. Roberts (Climate Dynamics, 2022)
Extra-tropical windstorms are one of the costliest natural hazards affecting Europe, and windstorms that develop a sting jet are extremely damaging. A sting jet is a mesoscale core of very high wind speeds that occurs in Shapiro–Keyser type cyclones, and high-resolution models are required to adequately model sting jets. Here, we develop a low-cost methodology to automatically detect sting jets, using the characteristic warm seclusion of Shapiro–Keyser cyclones and the slantwise descent of high wind speeds, within pan-European 2.2 km convection-permitting climate model (CPM) simulations. The representation of wind gusts is improved with respect to ERA-Interim reanalysis data compared to observations; this is linked to better representation of cold conveyor belts and sting jets in the CPM. Our analysis indicates that Shapiro–Keyser cyclones, and those that develop sting jets, are the most damaging windstorms in present and future climates. The frequency of extreme windstorms is projected to increase by 2100 and a large contribution comes from sting jet storms. Furthermore, extreme wind speeds and their future changes are underestimated in the global climate model (GCM) compared to the CPM. We conclude that the CPM adds value in the representation of extreme winds and surface wind gusts and can provide improved input for impact models compared to coarser resolution models.

Assessment of Australian Sea Lion Bycatch Mortality in a Gillnet Fishery, and Implementation and Evaluation of an Effective Mitigation Strategy - Simon D. Goldsworthy; Brad Page; Derek J. Hamer; Andrew D. Lowther; Peter D. Shaughnessy; Mark A. Hindell; Paul Burch; Daniel P. Costa; Shannon L. Fowler; Kristian Peters; Rebecca R. McIntosh; Frederic Bailleul; et al. (Frontiers in Marine Science, 2022)
Globally, the bycatch of marine mammals in fisheries represents the greatest source of human-caused mortality that threatens the sustainability of many populations and species. The Australian sea lion ( Neophoca cinerea ) is an endangered species, whose populations off South Australia (SA) have been subject to bycatch in a demersal gillnet fishery targeting sharks since the 1960s. A comprehensive assessment was undertaken of sea lion bycatch mortality that combined independent fishery observer data with species distribution models (underpinned by satellite tracking, abundance data and population modeling) to model the relationship between at-sea foraging effort and bycatch rate. Combined with the distribution of fishing effort, these models enabled the overall level of bycatch mortality to be estimated by age, sex and subpopulation, facilitating population viability analyses that indicated most subpopulations were declining, and subject to unsustainable levels of bycatch mortality. To reduce this mortality, the Australian Fisheries Management Authority implemented an Australian Sea Lion Management Strategy that included an independent observer program (ultimately 100% electronic monitoring of gillnet fishing off SA), permanent spatial gillnet closures around all sea lion breeding sites, bycatch mortality limits that triggered temporal (18 months) spatial closures when zone-specific bycatch trigger limits were reached, and incentives for gillnet fishers to switch to an alternate fishing method (longlines). The Strategy had immediate impacts on the fishery: it resulted in significant reductions in gillnet fishing effort and on the reported bycatch of sea lions. In the next decade, there was an estimated 98% reduction in sea lion bycatch mortality from gillnet interactions and an apparent stabilization of the decline in sea lion pup abundances at some impacted breeding sites. There was an almost complete transition in the fishery from gillnets to longlines, and fishing catches returned to pre-management levels. The successful implementation of management measures to mitigate sea lion bycatch mortality in the gillnet fishery off SA was rapid, science informed, adaptive, comprehensive, and backed by strong compliance and monitoring of the fishery. It provides an important case study which demonstrates how management measures can be effectively applied to mitigate bycatch mortality of marine mammals and other marine protected species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Use of plastid genome sequences in phylogeographic studies of tree species can be misleading without comprehensive sampling of co-occurring, related species - Patrick S. Fahey; Rachael M. Fowler; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Tree Genetics & Genomes, 2021)

Correction to: Large-scale dynamics have greater role than thermodynamics in driving precipitation extremes over India - Naveen Sudharsan; Subhankar Karmakar; Hayley J. Fowler; Vittal Hari (Climate Dynamics, 2021)

Marginal support for a trophic cascade among sympatric canids in peripheral wolf range - Nicholas L. Fowler; Todd M. Kautz; Tyler R. Petroelje; Clay M. Wilton; Kenneth F. Kellner; Daniel J. O’Brien; Bill Parsons; Dean E. Beyer; Jerrold L. Belant (Ecology, 2021)
Trophic cascades reportedly structure ecological communities through indirect species interactions. Though the predator–herbivore–autotroph relationship has received much attention, mechanistic evidence supporting intraguild trophic cascades is rare. We established 348 remote camera sites (1 August–5 September 2019) across seven study areas of varying wolf ( Canis lupus ) density including one study area where wolves were absent in northern Michigan, USA. Using multi‐species occupancy modeling at species‐relevant spatial scales, we evaluated the hypothesis that increased wolf occurrence suppresses coyote ( C . latrans ) occurrence with corresponding increased red fox ( Vulpes vulpes ) occurrence mediated by land cover edge density, human presence, and temporal partitioning. Remote cameras recorded >600,000 images and included 6,370, 10,137, and 4,876 detections of wolves, coyotes, and foxes, respectively. Fox occupancy probability was more than three times as high (0.29) at camera sites where wolves were present, relative to sites wolves were absent (0.09). Pairwise species interactions supported expected size‐based dominance patterns among canids and insignificant effects were directionally consistent with reported reduced strength of top‐down effects in peripheral wolf range. Increased edge density also increased co‐occurrence of coyote and wolves, likely a function of increased prey availability and refugia for coyotes. Though foxes occurred in spatial proximity to wolves, competition was limited by greater temporal partitioning than observed between coyotes and foxes that were spatially segregated. Collectively, our results provide marginal support for the reported trophic cascade among wolves, coyotes, and foxes wherein top‐down effects may be reduced near the edge of current wolf distributions. As predators continue to recolonize portions of their historic range, knowledge of the effects on intraguild predators has implications for species management and predicting prey population responses.

Invasion history shapes host transcriptomic response to a body‐snatching parasite - Zachary J. C. Tobias; Amy E. Fowler; April M. H. Blakeslee; John A. Darling; Mark E. Torchin; A. Whitman Miller; Gregory M. Ruiz; Carolyn K. Tepolt (Molecular Ecology, 2021)
By shuffling biogeographical distributions, biological invasions can both disrupt long‐standing associations between hosts and parasites and establish new ones. This creates natural experiments with which to study the ecology and evolution of host–parasite interactions. In estuaries of the Gulf of Mexico, the white‐fingered mud crab ( Rhithropanopeus harrisii ) is infected by a native parasitic barnacle, Loxothylacus panopaei (Rhizocephala), which manipulates host physiology and behaviour. In the 1960s, L . panopaei was introduced to the Chesapeake Bay and has since expanded along the southeastern Atlantic coast, while host populations in the northeast have so far been spared. We use this system to test the host's transcriptomic response to parasitic infection and investigate how this response varies with the parasite's invasion history, comparing populations representing (i) long‐term sympatry between host and parasite, (ii) new associations where the parasite has invaded during the last 60 years and (iii) naïve hosts without prior exposure. A comparison of parasitized and control crabs revealed a core response, with widespread downregulation of transcripts involved in immunity and moulting. The transcriptional response differed between hosts from the parasite's native range and where it is absent, consistent with previous observations of increased susceptibility in populations lacking exposure to the parasite. Crabs from the parasite's introduced range, where prevalence is highest, displayed the most dissimilar response, possibly reflecting immune priming. These results provide molecular evidence for parasitic manipulation of host phenotype and the role of gene regulation in mediating host–parasite interactions.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

New hourly extreme precipitation regions and regional annual probability estimates for the UK - Motasem M. Darwish; Mari R. Tye; Andreas F. Prein; Hayley J. Fowler; Stephen Blenkinsop; Murray Dale; Duncan Faulkner (International Journal of Climatology, 2021)
Recent flooding related to extreme precipitation in the UK has highlighted the importance of better understanding these events. Many studies have quantified annual exceedance probabilities (or return periods) for UK extreme daily precipitation using fixed regions (e.g., HadUKP) and region of interest (ROI) (e.g., Flood Estimation Handbook) approaches, although fewer have evaluated short‐duration events, which are important for flash flooding. Existing UK extreme precipitation regions are based on daily datasets which have different characteristics compared to sub‐daily extremes, and their application to quantify short‐duration extremes may therefore be inappropriate. We use a recently available, quality‐controlled hourly precipitation dataset for the UK from 1992 to 2014 to derive various extreme precipitation indices (e.g., annual maxima, 0.99 quantile) which are combined with additional climatological variables (e.g., temperature), geographical characteristics (e.g., latitude), and weather patterns (WPs) to characterize the UK hourly extreme precipitation climatology and to define five new hourly extreme regions. These regions fulfil regional homogeneity and discordancy statistical measures, and reflect the dynamical processes associated with the weather pattern categorisation defined over the UK and surrounding European area. Thereafter, we use regional frequency analysis (RFA) to fit generalized extreme value (GEV) and generalized Pareto (GP) distributions to 1 hr annual maxima (AMAX) and 0.99 quantile (Q99) precipitation, respectively, to calculate regional annual probability estimates (AEP) for 20%, 10%, and 2% (i.e., 5‐, 10‐, and 50‐year return periods). The new regions capture the spatial variation of hourly precipitation across the UK. Furthermore, the AEP estimates using both distributions are similar for each region. Finally, the WPs associated with the frequency and intensity of the most extreme hourly precipitation accumulations are not identical to results reported by others for daily precipitation.

Using a biophysical model to investigate connectivity between spawning grounds and nursery areas of King George whiting ( Sillaginodes punctatus : Perciformes) in South Australia’s gulfs - Troy A. Rogers; Ana Redondo Rodriguez; Anthony J. Fowler; Mark J. Doubell; Michael J. Drew; Michael A. Steer; Damian Matthews; Charles James; Bronwyn M. Gillanders (Fisheries Oceanography, 2021)
Many demersal marine fish species depend on a dispersive larval stage that connects geographically discrete sub‐populations. Understanding connectivity between these sub‐populations is necessary to determine stock structure, which identifies the appropriate spatial scale for fishery management. Such connectivity is poorly understood for King George whiting ( Sillaginodes punctatus ; Perciformes) in South Australia's gulf system, even though spawning grounds and nursery areas are adequately defined. In response to declines in commercial catches and estimated biomass, this study aimed to determine the most important spawning grounds and nursery areas to recruitment, and the connectivity between them. A biophysical model was seeded with particles according to the distribution and density of eggs throughout the spawning area in 2017 and 2018. Despite inter‐annual differences in the origins of particles, dispersal pathways and predicted settlement areas remained consistent between years. Predicted settlement was generally highest to nursery areas only short distances from regional spawning grounds, consistent with previous hydrodynamic models. However, the model also predicted that spawning in one region could contribute to recruitment in an adjacent region later in the spawning season, which aligned with the breakdown of thermohaline fronts at the entrance of each gulf. The connectivity between spawning grounds and nursery areas predicted by the model is supported by spatio‐temporal patterns in the otolith chemistry of pre‐flexion larvae and settled juveniles. Consequently, the most parsimonious explanation is that the populations of King George whiting in South Australia's gulf system constitute a single, panmictic stock, which has implications for fishery management.

Large-scale dynamics have greater role than thermodynamics in driving precipitation extremes over India - Naveen Sudharsan; Subhankar Karmakar; Hayley J. Fowler; Vittal Hari (Climate Dynamics, 2020)

Europe-wide precipitation projections at convection permitting scale with the Unified Model - Steven C. Chan; Elizabeth J. Kendon; Ségolène Berthou; Giorgia Fosser; Elizabeth Lewis; Hayley J. Fowler (Climate Dynamics, 2020)
For the first time, we analyze 2.2 km UK Met Office Unified Model convection-permitting model (CPM) projections for a pan-European domain. These new simulations represent a major increase in domain size, allowing us to examine the benefits of CPMs across a range of European climates. We find a change to the seasonality of extreme precipitation with warming. In particular, there is a relatively muted response for summer, which contrasts with much larger increases in autumn and winter. This flattens the hourly extreme precipitation seasonal cycle across Northern Europe which has a summer peak in the present climate. Over the Western Mediterranean, where autumn is the main extreme precipitation season, there is a regional increase in hourly extreme precipitation frequency, but local changes for lower precipitation thresholds are often insignificant. For mean precipitation, decreases are projected across Europe in summer, smaller decreases in autumn, and increases in winter; comparable changes are seen in the driving general circulation model (GCM) simulations. The winter mean increase is accompanied by a large decrease of winter mean snowfall. Comparing the driving GCM projections with the CPM ones, the CPMs show a robust enhanced intensification of precipitation extremes at the convection-permitting scale compared to coarser resolution climate model projections across various European regions for summer and autumn.

Atmospheric precursors for intense summer rainfall over the United Kingdom - Richard P. Allan; Stephen Blenkinsop; Hayley J. Fowler; Adrian J. Champion (International Journal of Climatology, 2020)
Intense sub‐daily summer rainfall is linked to flooding impacts in the United Kingdom. Characterizing the atmospheric conditions prior to the rainfall event can improve understanding of the large‐scale mechanisms involved. The most intense sub‐daily rainfall intensity data generated from rain gauge records across the United Kingdom over the period 1979–2014 are combined with fields from the ERA Interim reanalysis to characterize atmospheric conditions prior to heavy rainfall events. The 200 most intense 3‐hourly events for six UK regions are associated with negative anomalies in sea level pressure (

Plastid phylogenomic analysis of tribe Myoporeae (Scrophulariaceae) - Rachael M. Fowler; Todd G. B. McLay; Tanja M. Schuster; Bevan J. Buirchell; Daniel J. Murphy; Michael J. Bayly (Plant Systematics and Evolution, 2020)

Global distribution of the intensity and frequency of hourly precipitation and their responses to ENSO - Xiao-Feng Li; Stephen Blenkinsop; Renaud Barbero; Jingjing Yu; Elizabeth Lewis; Geert Lenderink; Selma Guerreiro; Steven Chan; Yafei Li; Haider Ali; Roberto Villalobos Herrera; Elizabeth Kendon; et al. (Climate Dynamics, 2020)
We investigate the global distribution of hourly precipitation and its connections with the El Niño–Southern Oscillation (ENSO) using both satellite precipitation estimates and the global sub-daily rainfall gauge dataset. Despite limited moisture availability over continental surfaces, we find that the highest mean and extreme hourly precipitation intensity (HPI) values are mainly located over continents rather than over oceans, a feature that is not evident in daily or coarser resolution data. After decomposing the total precipitation into the product of the number of wet hours (NWH) and HPI, we find that ENSO modulates total precipitation mainly through the NWH, while its effects on HPI are more limited. The contrasting responses to ENSO in NWH and HPI is particularly apparent at the rising branches of the Pacific and Atlantic Walker Circulations, and is also notable over land-based gauges in Australia, Malaysia, the USA, Japan and Europe across the whole distribution of hourly precipitation (i.e. extreme, moderate and light precipitation). These results provide new insights into the global precipitation distribution and its response to ENSO forcing.

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Responding to Climate Change: Participatory Evaluation of Adaptation Options for Key Marine Fisheries in Australia’s South East - Emily Ogier; Sarah Jennings; Anthony Fowler; Stewart Frusher; Caleb Gardner; Paul Hamer; Alistair J. Hobday; Adrian Linanne; Stephan Mayfield; Craig Mundy; Andrew Sullivan; Geoff Tuck; et al. (Frontiers in Marine Science, 2020)

UKGrsHP: a UK high-resolution gauge–radar–satellite merged hourly precipitation analysis dataset - Jingjing Yu; Xiao-Feng Li; Elizabeth Lewis; Stephen Blenkinsop; Hayley J. Fowler (Climate Dynamics, 2020)
There is an urgent need for high-quality and high-spatial-resolution hourly precipitation products around the globe, including the UK. Although hourly precipitation products exist for the UK, these either contain large errors, or are insufficient in spatial resolution. An efficient way to solve this is to develop a merged precipitation product that combines the information and benefits from multiple data sources, improving both the spatial resolution and accuracy of hourly precipitation estimates over the UK. In this study, we develop a UK high-resolution gauge–radar–satellite merged hourly precipitation analysis: the UKGrsHP. It covers the UK from 12.5° W to 3.5° E, 49° N–60° N, with a spatial resolution of 0.01° × 0.01° in latitude/longitude (equivalent to 1 km resolution in the mid-latitudes). An optimal interpolation (OI)–based multi-source merging scheme with compound strategy is developed and tested for producing the UKGrsHP. Three input data sources are used: gauge analysis data interpolated from 1903 quality-controlled hourly observations, the UK Nimrod radar precipitation analysis and the GSMaP global satellite precipitation analysis. Using independent tests against ~ 220 independent gauge observations on 1 year’s experimental UKGrsHP, covering the period from January to December 2014, we find that the final merged data performs better than three individual precipitation analyses used as inputs. A full version of the UKGrsHP starting in April 2004 is now under production, which will have wide applications in climate services and scientific research across multiple disciplines.

Discriminating Natal Source Populations of a Temperate Marine Fish Using Larval Otolith Chemistry - Troy A. Rogers; Anthony J. Fowler; Michael A. Steer; Bronwyn M. Gillanders (Frontiers in Marine Science, 2019)

Downscaling climate change of mean climatology and extremes of precipitation and temperature: Application to a Mediterranean climate basin - Rong Zhang; João Corte‐Real; Madalena Moreira; Chris Kilsby; Aidan Burton; Hayley J. Fowler; Stephen Blenkinsop; Stephen Birkinshaw; Nathan Forsythe; João P. Nunes; Elsa Sampaio (International Journal of Climatology, 2019)
Downscaling is usually necessary for robust hydrological impact assessments. This may be undertaken using a wide range of methods, including a combination of dynamical and statistical‐stochastic downscaling. This study uses the Spatial–Temporal Neyman‐Scott Rectangular Pulses model—RainSimV3, the precipitation‐conditioned daily weather generator—ICAAM‐WG, and the change factor approach for downscaling synthetic climate scenarios for robust hydrological impact assessment at middle‐sized basins. The ICAAM‐WG was developed based on the concept of the Climate Research Unit daily weather generator (CRU‐WG), motivated by the need for improved representation of heat waves by downscaling methods given the positive feedback between low soil moisture and high air temperature. We demonstrated the validity of the proposed methodology in the 705‐km 2 Mediterranean climate basin in southern Portugal. The results show that, for the control period 1980–2010, both RainSimV3 and ICAAM‐WG reproduced not only the mean climatology, but also extreme wet and low precipitation events, as well as the extremes of temperature and heat waves. We found that downscaling with ICAAM‐WG (SIM6), which uses second‐order autoregressive processes for the simulation of temperature during consecutive dry and wet days, outperformed ICAAM‐WG (SIM4), which used only first‐order autoregressive processes, leading to improved simulation of heat waves. ICAAM‐WG (SIM6) well reproduced observed heatwave extremes with return periods of up to 30 years; however, ICAAM‐WG (SIM4) overestimated these extremes substantially. This indicates the importance of incorporating second‐order autoregressive processes in the simulation of heatwave length. In the context of climate warming, the proposed methodology provides a tool to improve downscaled projections of future extremes with confidence intervals for not only wet events but also dry spells and heat waves.

Thermodynamic controls of the Western Tibetan Vortex on Tibetan air temperature - Xiao-Feng Li; Hayley J. Fowler; Jingjing Yu; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Climate change and summer thermal comfort in China - Qinqin Kong; Jingyun Zheng; Hayley J. Fowler; Quansheng Ge; Jianchao Xi (Theoretical and Applied Climatology, 2019)

Galactitol catabolism in Sinorhizobium meliloti is dependent on a chromosomally encoded sorbitol dehydrogenase and a pSymB-encoded operon necessary for tagatose catabolism - MacLean G. Kohlmeier; Catherine E. White; Jane E. Fowler; Turlough M. Finan; Ivan J. Oresnik (Molecular Genetics and Genomics, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Downscaling climate change of water availability, sediment yield and extreme events: Application to a Mediterranean climate basin - Rong Zhang; João Corte‐Real; Madalena Moreira; Chris Kilsby; Stephen Birkinshaw; Aidan Burton; Hayley J. Fowler; Nathan Forsythe; João Pedro Nunes; Elsa Sampaio; Francisco Lúcio dos Santos; Sandra Mourato (International Journal of Climatology, 2019)
A robust hydrological impact assessment is indispensable for mitigation and adaptation planning. This study presents an integrated modelling methodology for evaluating climate change impacts on water availability, sediment yield and extreme events at the catchment scale. We propose the use of the spatial–temporal Neyman–Scott Rectangular Pulses (STNSRP) model—RainSim V3 and the rainfall conditioned daily weather generator—ICAAM‐WG, as well as the physically based spatially distributed hydrological model—SHETRAN. The change factor approach was applied for obtaining unbiased rainfall and temperature statistics. The ICAAM‐WG was developed based on the modified Climate Research Unit daily Weather Generator (CRU‐WG). The methodology is proposed to generate synthetic series of hourly precipitation, daily temperature and potential evapotranspiration, hourly runoff and hourly sediment discharge. We demonstrated a possible application in a 705‐km 2 Mediterranean climate basin in southern Portugal. The case study showed the evaluation of future climate change impacts on annual and monthly water balance components and sediment yield, annual and seasonal flow duration curves, empirical extreme value distributions and the theoretical fits. It did not consider the possible uncertainty due to the limit of computational resources. The methodology can be well justified as follows: (a) the use of synthetic hourly instead of daily precipitation enables SHETRAN to be more capable of reproducing reliable storm runoff processes and the consequent sediment transport processes; (b) the use of SHETRAN makes possible the impact assessment to be accessible for any model grid square within the study basin; (c) the use of a statistical–stochastic downscaling method facilitates the generation of the synthetic series with unlimited length. It makes possible robust hydrological impact assessments if uncertainties related to the global climate model, regional climate model, greenhouse gas emission scenario, downscaling method, hydrological model and observational data are considered.

Weekly to multi‐month persistence in sets of daily weather patterns over Europe and the North Atlantic Ocean - Douglas Richardson; Christopher G. Kilsby; Hayley J. Fowler; András Bárdossy (International Journal of Climatology, 2019)
Persistence in time series of daily weather pattern (WP) classifications can provide useful information such as on the memory of broad‐scale atmospheric circulation. Despite this, research of WP persistence has lagged behind that exploring their frequencies of occurrence. We develop two methods for identifying persistence in a 167‐year time series of WPs defined over the North Atlantic–European domain. The first is an empirical counting technique used to find periods of persistence among sets of WPs, with the definition of persistence more relaxed than just consecutive occurrences. We then condition this method on the driest WPs to see if persistence can be used to identify historical drought. The second method uses a Markov model to assess if WP transition probabilities change when conditioned on information up to 20 days prior, without the need for estimating the large number of parameters usually required for high‐order Markov chains. Results are compared with a benchmark ensemble of synthetic time series generated using first‐order transition probabilities. We show that there were multi‐month periods when small sets of WPs dominated, and some of these periods coincided with notable meteorological events, including droughts and storms, such as the mid‐1990s drought in northern England and the Burn's Day Storm over southern Scotland in 1990. Some WPs also behave as “attractors,” showing increased probability of reoccurrence despite other WPs occurring in‐between. However, we find no link between the persistence statistics of each WP and their flow characteristics, except for those featuring an easterly flow over the United Kingdom, which are among the most persistent. The benchmark simulation ensemble is unable to reproduce many of the key persistence statistics of the observations, confirming that the persistence is a physical phenomenon. Finally, we discuss the potential processes underpinning WP persistence, such as the effects of large‐scale circulation patterns and land‐surface feedbacks.

Spatial and Temporal Associations Between Native Crabs and the Invading Green Porcelain Crab, Petrolisthes armatus, Throughout Its Northernmost Invaded Range - Kevin J. Mack; Robert D. Podolsky; Virginia Shervette; Amy E. Fowler; Dara H. Wilber (Estuaries and Coasts, 2019)

Contribution of large-scale midlatitude disturbances to hourly precipitation extremes in the United States - Renaud Barbero; John T. Abatzoglou; Hayley J. Fowler (Climate Dynamics, 2019)

Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Paul G. Thomson; Ashley M. Fowler; Andrew R. Davis; Charitha B. Pattiaratchi; David J. Booth (Frontiers in Marine Science, 2018)

Storylines: an alternative approach to representing uncertainty in physical aspects of climate change - Theodore G. Shepherd; Emily Boyd; Raphael A. Calel; Sandra C. Chapman; Suraje Dessai; Ioana M. Dima-West; Hayley J. Fowler; Rachel James; Douglas Maraun; Olivia Martius; Catherine A. Senior; Adam H. Sobel; et al. (Climatic Change, 2018)

New poleward observations of 30 tropical reef fishes in temperate southeastern Australia - Ashley M. Fowler; Kerryn Parkinson; David J. Booth (Marine Biodiversity, 2018)

Projected changes in extreme precipitation over Scotland and Northern England using a high-resolution regional climate model - Steven C. Chan; Ron Kahana; Elizabeth J. Kendon; Hayley J. Fowler (Climate Dynamics, 2018)

The Karakoram/Western Tibetan vortex: seasonal and year-to-year variability - Xiao-Feng Li; Hayley J. Fowler; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2018)

A regional frequency analysis of UK sub‐daily extreme precipitation and assessment of their seasonality - Motasem M. Darwish; Hayley J. Fowler; Stephen Blenkinsop; Mari R. Tye (International Journal of Climatology, 2018)
Floods related to extreme precipitation events, especially intense, short‐duration precipitation, may cause significant damage in urbanized areas, including transport infrastructure, electricity networks, and property. These events are expected to increase in frequency with climate change but their characteristics, at either hourly or multi‐hourly timescales, have been little studied due to short and poor quality data records. We examine annual maximum (AMAX) hourly and multi‐hourly (3, 6, 12, and 24 hr) precipitation accumulations in the United Kingdom using a quality‐controlled hourly precipitation data set for the period 1992–2014. We describe their seasonality and diurnal cycle and use a regional frequency analysis (RFA) approach with L ‐moments to produce at‐site return level estimates, and then use existing extreme precipitation regions to provide regional‐scale return levels. The analysis shows a clear seasonality and the dominant occurrence of short‐duration AMAX in summer with similar seasonality for 1 and 3 hr accumulation periods in some regions, while longer‐duration AMAX (12 and 24 hr) behave similarly to each other in all regions but are distributed over a longer period including late autumn and winter. The diurnal cycle of 1 hr AMAX indicates that most extremes occur during the afternoon, with a peak typically between 1400 and 1700, especially in southern and eastern regions. However, we also demonstrate that existing regions for UK daily extremes are not able to adequately reflect differences at shorter durations and that new regions should be created. These results provide new insights to help in designing urban drainage systems and infrastructure, including the need for new scaling relationships between sub‐daily and design accumulation periods.

Reply to comments on “Temperature‐extreme precipitation scaling: a two‐way causality?” - Geert Lenderink; Renaud Barbero; Seth Westra; Hayley J. Fowler (International Journal of Climatology, 2018)
In recent years, numerous studies have investigated the relationship of extreme precipitation intensities with temperature derived from a binning method using present‐day weather data. The aim of this approach is that these dependencies, or so‐called apparent scaling rates, provide insights on how precipitation extremes could evolve in the future climate. In a recent paper, Bao et al. showed that there is a large discrepancy between the present‐day apparent scaling rates—showing a negative dependency of daily rainfall extremes on temperature for Darwin—and the climate change response showing a substantial increase in daily rainfall extremes. Their results provide compelling evidence that it may not be straightforward to predict the climate change response from the temperature scaling. We agree with this statement, but disagree with the physical explanation put forward in that study and think that moisture limitations are the most likely cause. Therefore, we advocate the use of dew point temperatures in scaling studies as a much more direct proxy of the absolute humidity of the air in which precipitation extremes develop, which we think is physically more consistent with the underlying mechanism causing the increase in precipitation extremes with global warming.

Characterization of Behavioral, Signaling and Cytokine Alterations in a Rat Neurodevelopmental Model for Schizophrenia, and Their Reversal by the 5-HT6 Receptor Antagonist SB-399885 - Sinead E. Shortall; Ola H. Negm; Maxine Fowler; Lucy C. Fairclough; Patrick J. Tighe; Peter M. Wigmore; Madeleine V. King (Molecular Neurobiology, 2018)

Statistics of multi‐year droughts from the method for object‐based diagnostic evaluation - Abayomi A. Abatan; William J. Gutowski; Caspar M. Ammann; Laurna Kaatz; Barbara G. Brown; Lawrence Buja; Randy Bullock; Tressa Fowler; Eric Gilleland; John Halley Gotway (International Journal of Climatology, 2018)
This study uses the method for object‐based diagnostic evaluation (MODE) technique to examine and compare the statistics of drought attributes over the upper Colorado River basin (UCRB). The drought objects are based on the standardized precipitation index (SPI) and the standardized precipitation evapotranspiration index (SPEI) on a 36‐month timescale (SPI36 and SPEI36, respectively). The drought indicators are calculated using monthly precipitation as well as minimum and maximum temperatures from the Precipitation–Elevation Regression on Independent Slopes Model data sets from 1948 to 2012. MODE uses paired object attributes such as centroid distance, orientation angle, area ratio, and intersection area and a combination of parameter thresholds to determine the number of objects identified and retained in the merging and matching process in the two fields. Using MODE run with convolution radius of zero (no smoothing) and an area threshold of four grid points, this study computes and analyses object statistics including centroid locations, areas, and intensity percentiles. Results of the analysis show that SPI36 produces more drought objects than SPEI36. Although the spatial patterns are roughly similar leading up to almost similar statistics of object attributes, such as locations of the object centroids, the SPI36 produces higher percentile intensity of drought objects than does SPEI36, which is clearly obvious in the 90th percentile intensity of drought objects. The largest difference between SPEI36 and SPI36 occurs in the area of drought objects during the early 2000s when the region experienced multi‐year drought resulting from increased warming of the atmosphere. This study demonstrates the use of MODE as a tool to evaluate and monitor drought event over the UCRB.

Regional frequency analysis of extreme rainfall in Sicily (Italy) - Angelo Forestieri; Francesco Lo Conti; Stephen Blenkinsop; Marcella Cannarozzo; Hayley J. Fowler; Leonardo V. Noto (International Journal of Climatology, 2018)
Extreme rainfall events have large impacts on society and are likely to increase in intensity under climate change. For design and management decisions, particularly regarding hydraulic works, accurate estimates of precipitation magnitudes are needed at different durations. In this article, an objective approach of the regional frequency analysis (RFA) has been applied to precipitation data for the island of Sicily, Italy. Annual maximum series for rainfall with durations of 1, 3, 6, 12, and 24 h from about 130 rain gauges were used. The RFA has been implemented using principal component analysis (PCA) followed by a clustering analysis, through the k ‐means algorithm, to identify statistically homogeneous groups of stations for the derivation of regional growth curves. Three regional probability distributions were identified as appropriate from an initial wider selection of distributions and were compared – the three‐parameter log‐normal distribution (LN3), the generalized extreme value (GEV) distribution, and the two component extreme value (TCEV) distribution. The regional parameters of these distributions were estimated using L‐moments and considering a hierarchical approach. Finally, assessment of the accuracy of the growth curves was achieved by means of the relative bias and relative root‐mean‐square error (RMSE) using a simulation analysis of regional L‐moments. Results highlight that for the lower return periods, all distributions showed the same accuracy while for higher return periods the LN3 distribution provided the best result. The study provides an updated resource for the estimation of extreme precipitation quantiles for Sicily through the derivation of growth curves needed to obtain depth–duration–frequency (DDF) curves.

Temperature‐extreme precipitation scaling: a two‐way causality? - R. Barbero; S. Westra; G. Lenderink; H. J. Fowler (International Journal of Climatology, 2018)
Extreme precipitation events are widely thought to intensify in a warmer atmosphere through the Clausius‐Clapeyron equation. The temperature‐extreme precipitation scaling was proposed to analyse the temperature dependency of short‐duration extreme precipitation and since then, the concept has been widely used in climatology. Bao et al. (2017) suggest that the apparent scaling reflects not only how surface air properties affect extreme precipitation, but also reflects how synoptic conditions and localized cooling due to the storm itself affect the scaling – implying two‐way causality. We address here critical issues of this paper and provide evidence that dew point temperature drives extreme precipitation, with the direction of causality reversed only for the storm's peak intensity. This physical inference may serve as a basis to better quantify scaling rates and to help establish the relationship between extreme precipitation and environmental conditions in the current climate, and thereby provide insights into future changes to precipitation extremes due to climate change.

Sequence requirement of the ade6-4095 meiotic recombination hotspot in Schizosaccharomyces pombe - Steven J. Foulis; Kyle R. Fowler; Walter W. Steiner (Genetica, 2018)

A new precipitation and drought climatology based on weather patterns - Douglas Richardson; Hayley J. Fowler; Christopher G. Kilsby; Robert Neal (International Journal of Climatology, 2018)
Weather‐pattern, or weather‐type, classifications are a valuable tool in many applications as they characterize the broad‐scale atmospheric circulation over a given region. This study analyses the aspects of regional UK precipitation and meteorological drought climatology with respect to a new set of objectively defined weather patterns. These new patterns are currently being used by the Met Office in several probabilistic forecasting applications driven by ensemble forecasting systems. Weather pattern definitions and daily occurrences are mapped to Lamb weather types (LWTs), and parallels between the two classifications are drawn. Daily precipitation distributions are associated with each weather pattern and LWT. Standardized precipitation index (SPI) and drought severity index (DSI) series are calculated for a range of aggregation periods and seasons. Monthly weather‐pattern frequency anomalies are calculated for SPI wet and dry periods and for the 5% most intense DSI‐based drought months. The new weather‐pattern definitions and daily occurrences largely agree with their respective LWTs, allowing comparison between the two classifications. There is also broad agreement between weather pattern and LWT changes in frequencies. The new data set is shown to be adequate for precipitation‐based analyses in the UK, although a smaller set of clustered weather patterns is not. Furthermore, intra‐pattern precipitation variability is lower in the new classification compared to the LWTs, which is an advantage in this context. Six of the new weather patterns are associated with drought over the entire UK, with several other patterns linked to regional drought. It is demonstrated that the new data set of weather patterns offers a new opportunity for classification‐based analyses in the UK.

Assessing the threat of future megadrought in Iberia - Selma B. Guerreiro; Chris Kilsby; Hayley J. Fowler (International Journal of Climatology, 2017)
Water scarcity is a critical issue in Iberia but few studies have investigated future drought over the region. The few that do are continental or global studies and do not report the range of possible future projections. In this paper, historical drought and future projections of drought were examined, using observed and downscaled rainfall data from climate models, for the main Iberian international basins (Douro, Tagus and Guadiana). Two drought indices were used, the standardized precipitation index ( SPI ) and the drought severity index ( DSI ). However, problems were found in the distribution fitting required for the calculation of SPI which render this index inadequate for assessing droughts in Iberia. The skill of CMIP5 climate models in representing historical drought for the Douro, Tagus and Guadiana is very variable with some not showing enough persistence of dry conditions, and others simulating droughts that are too long and too severe. Nevertheless, the observed range of drought conditions for these basins was encompassed by the ensemble members. Furthermore, we found no relationship between performance in simulating mean large‐scale circulation and model ability to reproduce the historical drought characteristics for the region. All models project an intensification of drought conditions for the three basins. However, some only project small increases, while most project extreme multi‐year droughts by the end of the century. We found that climate model future projections are neither related to their performance in simulating historical drought nor to their large‐scale circulation patterns. This result emphasises the need for climate change impact studies to take into account the whole range of climate model projections in order to provide the best information for robust adaptation. Choosing one or a subset of climate models based on historical performance would not lead to a credible and justified reduction in uncertainty.

Erratum to: Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Metabolic Profiling of Human Long-Term Liver Models and Hepatic Clearance Predictions from In Vitro Data Using Nonlinear Mixed-Effects Modeling - Nicole A. Kratochwil; Christophe Meille; Stephen Fowler; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Sandrine Simon; Isabelle Walter; Claudia McGinnis; Johanna Walther; Brian Leonard; Miriam Triyatni; et al. (The AAPS Journal, 2017)

Speed breeding for multiple disease resistance in barley - Lee T. Hickey; Silvia E. Germán; Silvia A. Pereyra; Juan E. Diaz; Laura A. Ziems; Ryan A. Fowler; Greg J. Platz; Jerome D. Franckowiak; Mark J. Dieters (Euphytica, 2017)

Pathogenic variation of Pyrenophora teres f. teres in Australia - R. A. Fowler; G. J. Platz; K. L. Bell; S. E. H. Fletcher; J. D. Franckowiak; L. T. Hickey (Australasian Plant Pathology, 2017)

Humanizing the zebrafish liver shifts drug metabolic profiles and improves pharmacokinetics of CYP3A4 substrates - Kar Lai Poon; Xingang Wang; Ashley S. Ng; Wei Huang Goh; Claudia McGinnis; Stephen Fowler; Tom J. Carney; Haishan Wang; Phillip W. Ingham (Archives of Toxicology, 2017)

Quality‐control of an hourly rainfall dataset and climatology of extremes for the UK - Stephen Blenkinsop; Elizabeth Lewis; Steven C. Chan; Hayley J. Fowler (International Journal of Climatology, 2017)
Sub‐daily rainfall extremes may be associated with flash flooding, particularly in urban areas but, compared with extremes on daily timescales, have been relatively little studied in many regions. This paper describes a new, hourly rainfall dataset for the UK based on ∼1600 rain gauges from three different data sources. This includes tipping bucket rain gauge data from the UK Environment Agency (EA), which has been collected for operational purposes, principally flood forecasting. Significant problems in the use of such data for the analysis of extreme events include the recording of accumulated totals, high frequency bucket tips, rain gauge recording errors and the non‐operation of gauges. Given the prospect of an intensification of short‐duration rainfall in a warming climate, the identification of such errors is essential if sub‐daily datasets are to be used to better understand extreme events. We therefore first describe a series of procedures developed to quality control this new dataset. We then analyse ∼380 gauges with near‐complete hourly records for 1992–2011 and map the seasonal climatology of intense rainfall based on UK hourly extremes using annual maxima, n ‐largest events and fixed threshold approaches. We find that the highest frequencies and intensities of hourly extreme rainfall occur during summer when the usual orographically defined pattern of extreme rainfall is replaced by a weaker, north–south pattern. A strong diurnal cycle in hourly extremes, peaking in late afternoon to early evening, is also identified in summer and, for some areas, in spring. This likely reflects the different mechanisms that generate sub‐daily rainfall, with convection dominating during summer. The resulting quality‐controlled hourly rainfall dataset will provide considerable value in several contexts, including the development of standard, globally applicable quality‐control procedures for sub‐daily data, the validation of the new generation of very high‐resolution climate models and improved understanding of the drivers of extreme rainfall.

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Navigating the complexity of ecological stability - Ian Donohue; Helmut Hillebrand; José M. Montoya; Owen L. Petchey; Stuart L. Pimm; Mike S. Fowler; Kevin Healy; Andrew L. Jackson; Miguel Lurgi; Deirdre McClean; Nessa E. O'Connor; Eoin J. O'Gorman; et al. (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.

Land colonisation by fish is associated with predictable changes in life history - Edward R. M. Platt; Ashley M. Fowler; Terry J. Ord (Oecologia, 2016)

Effects of Morphine on Behavioral Task Performance in SIV-Infected Rhesus Macaques - Joanne K. Marcario; Gurudutt Pendyala; Mariam Riazi; Kandace Fleming; Janet Marquis; Shannon Callen; Steven J. Lisco; Stephen C. Fowler; Paul D. Cheney; Shilpa J. Buch (Journal of Neuroimmune Pharmacology, 2016)

Characterizing Uncertainty of the Hydrologic Impacts of Climate Change - Martyn P. Clark; Robert L. Wilby; Ethan D. Gutmann; Julie A. Vano; Subhrendu Gangopadhyay; Andrew W. Wood; Hayley J. Fowler; Christel Prudhomme; Jeffrey R. Arnold; Levi D. Brekke (Current Climate Change Reports, 2016)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Rainfall in Iberian transnational basins: a drier future for the Douro, Tagus and Guadiana? - Selma B. Guerreiro; Chris G. Kilsby; Hayley J. Fowler (Climatic Change, 2016)

hERG Blockade by Iboga Alkaloids - Kenneth Alper; Rong Bai; Nian Liu; Steven J. Fowler; Xi-Ping Huang; Silvia G. Priori; Yanfei Ruan (Cardiovascular Toxicology, 2016)

Genomic deletions and mutations resulting in the loss of eight genes reduce the in vivo replication capacity of Meleagrid herpesvirus 1 - Timothy J. Mahony; Robyn N. Hall; Stephen Walkden-Brown; Joanne Meers; Jennifer L. Gravel; Lani West; Vanessa Hardy; A.F.M. Fakhrul Islam; Elizabeth V. Fowler; Neena Mitter (Virus Genes, 2015)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

20th International Chromosome Conference (ICCXX) - Darren K. Griffin; Katie E. Fowler; Peter J. I. Ellis; Dean A. Jackson (Chromosome Research, 2015)

Spatial variation in shape of otoliths for southern garfish Hyporhamphus melanochir – Contribution to stock structure - Michael A. Steer; Anthony J. Fowler (Marine Biology Research, 2015)

Latitudinal shifts in coral reef fishes: why some species do and others do not shift - David A Feary; Morgan S Pratchett; Micheal J Emslie; Ashley M Fowler; Will F Figueira; Osmar J Luiz; Yohei Nakamura; David J Booth (Fish and Fisheries, 2014)
Climate change is resulting in rapid poleward shifts in the geographical distribution of many tropical fish species, but it is equally apparent that some fishes are failing to exhibit expected shifts in their geographical distribution. There is still little understanding of the species‐specific traits that may constrain or promote successful establishment of populations in temperate regions. We review the factors likely to affect population establishment, including larval supply, settlement and post‐settlement processes. In addition, we conduct meta‐analyses on existing and new data to examine relationships between species‐specific traits and vagrancy. We show that tropical vagrant species are more likely to originate from high‐latitude populations, while at the demographic level, tropical fish species with large body size, high swimming ability, large size at settlement and pelagic spawning behaviour are more likely to show successful settlement into temperate habitats. We also show that both habitat and food limitation at settlement and within juvenile stages may constrain tropical vagrant communities to those species with medium to low reliance on coral resources.

The role of CITES in the conservation of marine fishes subject to international trade - Amanda C J Vincent; Yvonne J Sadovy de Mitcheson; Sarah L Fowler; Susan Lieberman (Fish and Fisheries, 2014)
All possible tools need to be marshalled for marine fish conservation. Yet controversy has swirled around what role, if any, the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) should play for marine fishes. This paper analyses the relevance and applicability of CITES as a complementary tool for fisheries management. CITES currently regulates the international trade of very few marine fish species, by listing them in its Appendices. After the first meeting of the Parties (member countries) in 1976, no new marine fish taxa were added to the CITES Appendices until 2002, when Parties agreed to act to ensure sustainable and legal international trade in seahorses ( Hippocampus spp.) and two species of sharks. Progress has continued haltingly, adding only one more shark, humphead wrasse ( Cheilinus undulatus ) and sawfishes by 2012. Parties voice concerns that may include inadequate data, applicability of CITES listing criteria, roles of national fisheries agencies, enforcement challenges, CITES ' lack of experience with marine fishes, and/or identification and by‐catch problems. A common query is the relationship between CITES and other international agreements. Yet all these arguments can be countered, revealing CITES to be a relevant and appropriate instrument for promoting sound marine fisheries management. In reality, Parties that cannot implement CITES effectively for marine fishes will also need help to manage their fisheries sustainably. CITES action complements and supports other international fisheries management measures. As CITES engages with more marine fish listings, there will be greater scope to analyse its effectiveness in supporting different taxa in different contexts.

Age validation, growth and population characteristics of greenback flounder ( Rhombosolea tapirina ) in a large temperate estuary - Jason Earl; Anthony J Fowler; Qifeng Ye; Sabine Dittmann (New Zealand Journal of Marine and Freshwater Research, 2014)
The greenback flounder ( Rhombosolea tapirina ) is an important fishery species in southern Australia and New Zealand, whose demographic processes are poorly understood. This study developed an ageing protocol based on otolith interpretation and provided estimates of age‐based data for an exploited population in the estuary of Australia's largest river system. The otoliths fulfilled three criteria that established their usefulness for ageing. Estimates of size and age were used to generate von Bertalanffy growth curves for male and female fish sampled from two areas within the estuary. There were no differences in growth between the sexes, despite the strong bias in number towards female fish. Spatial differences in growth were marginal. Populations involved only a few young age classes. Such truncation may relate to the fishery, to movement of older fish out of the system, or to recent poor environmental conditions limiting spawning and early life survivorship.

Objective classification of extreme rainfall regions for the UK and updated estimates of trends in regional extreme rainfall - Mari R. Jones; Stephen Blenkinsop; Hayley J. Fowler; Christopher G. Kilsby (International Journal of Climatology, 2014)
Extreme rainfall events pose considerable threats to society and critical infrastructure yet, by definitions, these events are rare. Reliable estimates of the likelihood of such events are required to assist with impact quantification and risk management. Regional frequency analysis of pooled extreme rainfall to estimate the likely impacts of a changing climate is a well established method to assess the probability of these extremes. Previous analyses of country‐wide changes to UK extreme daily rainfall have used the 9 Hadley UK Precipitation ( HadUKP ) regions (Alexander and Jones, 2000), which are not appropriate for use with extremes. While these characterize well the mean daily intensity and frequency within each region, extreme rainfall climatology differs from that of the mean characteristics. As a result the existing HadUKP regions do not represent extreme rainfall behaviour adequately, with regard to the frequency, intensity or timing of extreme events. Focussing on many extreme rainfall characteristics, such as the seasonal timing and magnitude of maxima, this article presents a formal representation of extreme regions which specifically describe extreme spatial and temporal characteristics. The article concludes with a brief exploration of improved event estimation using these extreme rainfall regions. The new regional definitions provide clearer upward trends in annual maxima over the period 1961–2010 than those estimated using the HadUKP regional pools. © 2013 Royal Meteorological Society

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Fish assemblages associated with oil industry structures on the continental shelf of north‐western Australia - N. Pradella; A. M. Fowler; D. J. Booth; P. I. Macreadie (Journal of Fish Biology, 2014)
This study provides the first assessment of fish associations with oil and gas structures located in deep water (85–175 m) on Australia's north‐west continental shelf, using rare oil industry video footage obtained from remotely operated vehicles. A diverse range of taxa were observed associating with the structures, including reef‐dependent species and transient pelagic species. Ten commercially fished species were observed, the most abundant of which was Lutjanus argentimaculatus , with an estimated biomass for the two deepest structures (Goodwyn and Echo) of 109 kg.

Pathogenicity of Blumeria graminis f. sp. hordei in Australia in 2010 and 2011 - A. Dreiseitl; R. A. Fowler; G. J. Platz (Australasian Plant Pathology, 2013)

Role of α5* nicotinic acetylcholine receptors in the effects of acute and chronic nicotine treatment on brain reward function in mice - Christie D. Fowler; Luis Tuesta; Paul J. Kenny (Psychopharmacology, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

Development and characterization of 21 polymorphic microsatellite markers for the barren-ground shrew, Sorex ugyunak (Mammalia: Sorcidae), through next-generation sequencing, and cross-species amplification in the masked shrew, S. cinereus - S. A. Sonsthagen; G. K. Sage; M. Fowler; A. G. Hope; J. A. Cook; S. L. Talbot (Conservation Genetics Resources, 2013)

Potential effects of climate change on biological control systems: case studies from New Zealand - P. J. Gerard; J. R. F. Barringer; J. G. Charles; S. V. Fowler; J. M. Kean; C. B. Phillips; A. B. Tait; G. P. Walker (BioControl, 2013)

An assessment of changes in seasonal and annual extreme rainfall in the UK between 1961 and 2009 - Mari R. Jones; Hayley J. Fowler; Christopher G. Kilsby; Stephen Blenkinsop (International Journal of Climatology, 2013)
There is a growing body of evidence supporting the Intergovernmental Panel on Climate Change's contestation that changes to hydrological extremes as a result of anthropogenic climate change are likely. There is also a growing level of concern among water resource managers about the nature of these changes and how we might adapt our behaviour to accommodate them. In particular, extreme multi‐day rainfall events have been a significant contributing factor to the severe flood events of recent years. Here we provide an updated study of extreme rainfall in the UK, focussing on changes to seasonal and annual maxima over the period 1961‐2009. We employ regional frequency analysis to examine changes in the magnitude of estimated return periods obtained from generalized extreme value distribution curves. Return period estimates are analysed using both the full record and using 10 year intervals to determine the relative importance of natural variability and long‐term changes in extreme rainfall distribution. The magnitude of changes in estimated return periods are spatially varied, and dominated in northern and western parts of the UK by a periodic forcing such as the North Atlantic Oscillation (NAO), superimposed on normal seasonal fluctuations. In contrast, seasonality has the greatest influence on event magnitude in the south and east. We confirm that previously reported increases in spring and autumn extreme rainfall events have continued. Similarly, longer duration winter events have continued to increase in intensity, with a decrease in return period estimate from a 25‐year to around a 5‐year event over the full 50 years of record in parts of Scotland and Southwest England. In contrast, short‐duration summer rainfall events have continued to decline in intensity, whereas longer duration events appear to be increasing in intensity. These results may have significant implications for flood defence design and planning, as well as to agricultural practices which may be sensitive to extreme rainfall. Copyright © 2012 Royal Meteorological Society

Mobile receivers: releasing the mooring to ‘see’ where fish go - Sean A. Hayes; Nicole M. Teutschel; Cyril J. Michel; Cory Champagne; Patrick W. Robinson; Melinda Fowler; Tina Yack; David K. Mellinger; Samantha Simmons; Daniel P. Costa; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

How well do sunken vessels approximate fish assemblages on coral reefs? Conservation implications of vessel-reef deployments - A. M. Fowler; D. J. Booth (Marine Biology, 2012)

The spawning dynamics of snapper ( Chrysophrys auratus ) in northern Spencer Gulf, South Australia - Richard J Saunders; Anthony J Fowler; Bronwyn M Gillanders (New Zealand Journal of Marine and Freshwater Research, 2012)
This study investigated the inter‐ and intra‐annual variation in the spawning dynamics of snapper ( Chrysophrys auratus ). Reproductive samples from northern Spencer Gulf, South Australia were collected over three seasons (2005/06, 2006/07 and 2007/08) and were analysed macro and microscopically. Spawning activity was determined by calculating estimates of spawning fraction and batch fecundities. The onset of spawning occurred in November but varied between years and corresponded with times when water temperature was between 18 °C and 20 °C. The length of the spawning season also differed between years. In each year the peak spawning activity occurred during December when fish spawned almost daily. Spawning frequency and relative batch size did not differ between the first two spawning seasons but, in the third season, batch size was considerably greater and spawning fractionally lower. These results are contrasted with a known recruitment of 0+ over the three years of the study.

Utility of genetically modified mice for understanding the neurobiology of substance use disorders - Christie D. Fowler; Paul J. Kenny (Human Genetics, 2012)

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

Blue shark Prionace glauca fin‐to‐carcass‐mass ratios in Spain and implications for finning ban enforcement - J. Santana‐Garcon; S. Fordham; S. Fowler (Journal of Fish Biology, 2012)
This study examines the processing of fins from blue sharks Prionace glauca caught by the Spanish longline fleet and landed in Vigo, Spain, and implications of these practices for enforcing the E.U. ban on shark finning, which relies on a maximum fin‐to‐carcass‐mass ratio. Two major sources of variability in fin‐to‐carcass ratios are quantified and discussed: (1) the fin set (type and number of fins retained from each shark) and (2) the cutting method used to separate fins from carcasses. The significant differences in fin‐to‐carcass‐mass ratios between fin sets or cutting procedure demonstrates that the ratio limit is problematic and, conclusively, in order to facilitate proper enforcement, fishermen should be required to land all sharks with the fins still naturally attached to the bodies.

Opportunities from Remote Sensing for Supporting Water Resources Management in Village/Valley Scale Catchments in the Upper Indus Basin - Nathan Forsythe; Hayley J. Fowler; Chris G. Kilsby; David R. Archer (Water Resources Management, 2012)

A multi-model ensemble of downscaled spatial climate change scenarios for the Dommel catchment, Western Europe - Michelle T. H. van Vliet; Stephen Blenkinsop; Aidan Burton; Colin Harpham; Hans Peter Broers; Hayley J. Fowler (Climatic Change, 2012)

Evidence of sustained populations of a small reef fish on artificial structures. Does depth affect production on artificial reefs? - A. M. Fowler; D. J. Booth (Journal of Fish Biology, 2012)
The length frequencies and age structures of resident Pseudanthias rubrizonatus ( n = 407), a small protogynous serranid, were measured at four isolated artificial structures on the continental shelf of north‐western Australia between June and August 2008, to determine whether these structures supported full (complete size and age‐structured) populations of this species. The artificial structures were located in depths between 82 and 135 m, and growth rates of juveniles and adults, and body condition of adults, were compared among structures to determine the effect of depth on potential production. All life‐history stages, including recently settled juveniles, females and terminal males, of P . rubrizonatus were caught, ranging in standard length ( L s ) from 16·9 to 96·5 mm. Presumed ages estimated from whole and sectioned otoliths ranged between 22 days and 5 years, and parameter ± s.e. estimates of the von Bertalanffy growth model were L ∞ = 152 ± 34 mm, k = 0·15(±0·05) and t 0 = −1·15(±0·15). Estimated annual growth rates were similar between shallow and deep artificial structures; however, otolith lengths and recent growth of juveniles differed among individual structures, irrespective of depth. The artificial structures therefore sustained full populations of P . rubrizonatus , from recently settled juveniles through to adults; however, confirmation of the maximum age attainable for the species is required from natural populations. Depth placement of artificial reefs may not affect the production of fish species with naturally wide depth ranges.

Modelling the acquisition times of CORONA satellite photographs: accuracy and application - M. J. F. Fowler (International Journal of Remote Sensing, 2011)

Influence of insects and fungal pathogens on individual and population parameters of Cirsium arvense in its native and introduced ranges - Michael G. Cripps; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler; Grant R. Edwards (Biological Invasions, 2011)

Dry deposition of ammonia gas drives species change faster than wet deposition of ammonium ions: evidence from a long‐term field manipulation - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; John Neil Cape; Alan Crossley; Sarah Leeson; Mark A. Sutton; Netty van Dijk; David Fowler (Global Change Biology, 2011)
Although the effects of atmospheric nitrogen deposition on species composition are relatively well known, the roles of the different forms of nitrogen, in particular gaseous ammonia ( NH 3 ), have not been tested in the field. Since 2002, we have manipulated the form of N deposition to an ombrotrophic bog, W him, on deep peat in southern S cotland, with low ambient N (wet + dry = 8 kg N ha −1 yr −1 ) and S (4 kg S ha −1 yr −1 ) deposition. A gradient of ammonia ( NH 3 , dry N ), from 70 kg N ha −1 yr −1 down to background, 3–4 kg N ha −1 yr −1 was generated by free air release. Wet ammonium ( NH 4 + , wet N) was provided to replicate plots in a fine rainwater spray ( NH 4 Cl at +8, +24, +56 kg N ha −1 yr −1 ). Automated treatments are coupled to meteorological conditions, in a globally unique, field experiment. Ammonia concentrations were converted to NH 3 ‐ N deposition (kg N ha −1 ) using a site/vegetation specific parameterization. Within 3 years, exposure to relatively modest deposition of NH 3 , 20–56 kg NH 3 ‐N ha −1 yr −1 led to dramatic reductions in species cover, with almost total loss of C alluna vulgaris , S phagnum capillifolium and C ladonia portentosa . These effects appear to result from direct foliar uptake and interaction with abiotic and biotic stresses, rather than via effects on the soil. Additional wet N by contrast, significantly increased C alluna cover after 5 years at the 56 kg N dose, but reduced cover of S phagnum and C ladonia . Cover reductions caused by wet N were significantly different from and much smaller than those caused by equivalent dry N doses. The effects of gaseous NH 3 described here, highlight the potential for ammonia to destroy acid heathland and peat bog ecosystems. Separating the effects of gaseous ammonia and wet ammonium deposition, for a peat bog, has significant implications for regulatory bodies and conservation agencies.

Variation in productivity of a key snapper, Chrysophrys auratus , fishery related to recruitment and fleet dynamics - A. J. FOWLER; D. McGLENNON (Fisheries Management and Ecology, 2011)
Temporal variation in production of the Chrysophrys auratus (Forster) fishery of Northern Spencer Gulf, South Australia, between 1984 and 2009 was investigated using commercial fishery statistics and estimates of age and size structures from market sampling. Fishery production was divisible into two periods, i.e. from 1984 to early 2000s and the middle to late 2000s. During the former, cycles in production were relatable to variable fishable biomass. Age structures that displayed considerable differences in age class strength reflected interannual variation in juvenile recruitment, which resulted in high variability in the strength of year classes entering the fishery. Periodic strong year classes were the major influence on fishable biomass as they passed through the population over numerous years. For the latter period, fishery statistics were conflicting as catches and effort were relatively low, whilst the estimates of catch per unit effort (CPUE) were consistently high. These statistics reflect a considerable change to the structure of the fishery that involved a reduction in number of fishers and fishing effort. The fishery statistics may indicate hyperstability, with CPUE estimates remaining high despite declining biomass because of the aggregative behaviour of the fish and the efficiency of remaining fishers.

The Harvest Experiment LIDAR System: Water Level Measurement Device Comparison for Jason-1 and Jason-2/OSTM Calibration - Scott A. Washburn; Bruce J. Haines; George H. Born; Charles Fowler (Marine Geodesy, 2011)

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

Temporal variation in feeding behaviour and trophic ecology of the temperate hemiramphid, Hyporhamphus melanochir - Jason Earl; Anthony J. Fowler; Sabine Dittmann (Environmental Biology of Fishes, 2011)

Stock discrimination of Southern Garfish (Hyporhamphus melanochir) by stable isotope ratio analysis of otolith aragonite - Mike A. Steer; Galen P. Halverson; Anthony J. Fowler; Bronwyn M. Gillanders (Environmental Biology of Fishes, 2010)

Enemy release does not increase performance of Cirsium arvense in New Zealand - Michael G. Cripps; Grant R. Edwards; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler (Plant Ecology, 2010)

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8 - S. P. Kuster; S. Drews; K. Green; J. Blair; I. Davis; J. Downey; R. Fowler; K. Katz; S. Lapinsky; D. McRitchie; J. Pataki; J. Powis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

Are prediction models for Lynch syndrome valid for probands with endometrial cancer? - Floor J. Backes; Heather Hampel; Katherine A. Backes; Luis Vaccarello; George Lewandowski; Jeffrey A. Bell; Gary C. Reid; Larry J. Copeland; Jeffrey M. Fowler; David E. Cohn (Familial Cancer, 2009)

Comparative expression of Cbf genes in the Triticeae under different acclimation induction temperatures - Chiara Campoli; Maria A. Matus-Cádiz; Curtis J. Pozniak; Luigi Cattivelli; D. Brian Fowler (Molecular Genetics and Genomics, 2009)

Age‐related movement patterns and population structuring in southern garfish, Hyporhamphus melanochir , inferred from otolith chemistry - M. A. STEER; A. J. FOWLER; B. M. GILLANDERS (Fisheries Management and Ecology, 2009)
The southern garfish, Hyporhamphus melanochir (Val.), is an important inshore fishery species in South Australia. Over the past few years there have been concerns with this fishery, which is now considered to be over‐exploited. Currently, the fishery is assumed to consist of two separate stocks, but there is no understanding of movement patterns both within and between these two stocks to justify this assumption. Otolith chemistry was used to infer age‐related patterns of movement, delineate potential sub‐populations and determine the extent of mixing within South Australian coastal waters. Results indicated that the population structuring of garfish is more complex than previously assumed and it seems that stocks can be discriminated at a much finer spatial scale. Garfish collected from sites separated by 7 Li, 24 Mg, 55 Mn, 88 Sr and 138 Ba) in their otoliths, especially during their second year of growth, indicating that they had inhabited different water bodies. From a broader perspective, South Australian garfish can be partitioned into six regional components with various levels of inter‐mixing. From these results, it was suggested that assessment and management of the fishery may have to be restructured to align with the smaller spatial units.

Multi‐model ensemble estimates of climate change impacts on UK seasonal precipitation extremes - H. J. Fowler; M. Ekström (International Journal of Climatology, 2009)
Thirteen regional climate model (RCM) integrations from the Prediction of Regional Scenarios and Uncertainties for Defining European Climate change risks and Effects (PRUDENCE) ensemble are used together with extreme value analysis to assess changes to seasonal precipitation extremes in nine UK rainfall regions by 2070–2100 under the SRES A2 emissions scenario. Model weights are based on similarities between observed and modelled UK extreme precipitation calculated for a combination of (1) spatial characteristics: the semi‐variogram parameters sill and range, and (2) the discrepancy in the regional median seasonal maxima. These weights are used to combine individual RCM bootstrap samples to provide multi‐model ensemble estimates of percent change in the return value magnitudes of regional extremes. The contribution of global climate model (GCM) and RCM combinations to model structural uncertainty is also investigated. The multi‐model ensembles project increases across the UK in winter, spring and autumn extreme precipitation; although there is uncertainty in the absolute magnitude of increases, these range from 5 to 30% depending upon region and season. In summer, model predictions span the zero change line, although there is low confidence due to poor model performance. RCM performance is shown to be highly variable; extremes are well simulated in winter and very poorly simulated in summer. The ensemble distributions are wider (projections are more uncertain) for shorter duration extremes (e.g. 1 day) and higher return periods (e.g. 25 year). There are rather limited differences in the weighted and unweighted multi‐model ensembles, perhaps a consequence of the lack of model independence between ensemble members. The largest contribution to uncertainty in the multi‐model ensembles comes from the lateral boundary conditions used by RCMs included in the ensemble. Therefore, the uncertainty bounds shown here are conservative despite the relatively large number of RCMs contributing to the multi‐model ensemble distribution. Copyright © 2009 Royal Meteorological Society

Climate extremes: progress and future directions - Lisa V. Alexander; Nigel Tapper; Xuebin Zhang; Hayley J. Fowler; Claudia Tebaldi; Amanda Lynch (International Journal of Climatology, 2009)

Transgenic mice expressing the Peripherin-EGFP genomic reporter display intrinsic peripheral nervous system fluorescence - Samuel McLenachan; Yona Goldshmit; Kerry J. Fowler; Lucille Voullaire; Timothy P. Holloway; Ann M. Turnley; Panos A. Ioannou; Joseph P. Sarsero (Transgenic Research, 2008)

Mathematical Analysis of a Model of River Channel Formation - J. I. Díaz; A. C. Fowler; A. I. Muñoz; E. Schiavi (Pure and Applied Geophysics, 2008)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

ENSO history recorded in Agathis australis (kauri) tree rings. Part A: kauri's potential as an ENSO proxy - A. M. Fowler; G. Boswijk; J. Gergis; A. Lorrey (International Journal of Climatology, 2008)
Although many of the main characteristics of the El Niño‐Southern Oscillation (ENSO) phenomenon have been established, uncertainties remain concerning its multidecadal‐ to millennial‐scale evolution. Because of the shortness of the instrumental record, we need to resort to proxy‐based reconstructions to investigate ENSO's history prior to the mid 19th century, but the available proxy data is limited in both time and space. Here we investigate the potential for ENSO reconstruction from the tree rings of Agathis australis (kauri). Kauri is a long‐lived endemic New Zealand conifer and grows in an ENSO teleconnection region not previously represented in ENSO multi‐proxy studies. A high quality 423 year kauri regional master chronology (AD 1580–2002) is constructed. Statistical analysis of the period AD 1876–2002 confirms previous findings that kauri tree rings carry a strong regional‐scale climate signal and that ENSO is a significant contributor (predominantly via the western pole of the Southern Oscillation). Kauri carries a signal of both ENSO phases, but with a slight El Niño bias. Growth sensitivity is primarily registered through a five‐season window, extending from March (prior to growth initiation in September) through to the following May, with strongest relationships across the middle three seasons (June–February). Relationships appear to be stationary. We conclude that kauri has sufficient ENSO event capture skill to make it a useful addition to future multi‐proxy ENSO reconstruction efforts. It may also have potential for stand‐alone reconstruction of multidecadal‐ to millennial‐scale evolution of ENSO activity, especially ENSO robustness. Copyright © 2007 Royal Meteorological Society

The Pharmacology of the Cannabinoid System—A Question of Efficacy and Selectivity - Christopher J. Fowler (Molecular Neurobiology, 2007)

Beyond the downscaling comparison study - Hayley J Fowler; Rob L Wilby (International Journal of Climatology, 2007)

Linking climate change modelling to impacts studies: recent advances in downscaling techniques for hydrological modelling - H. J. Fowler; S. Blenkinsop; C. Tebaldi (International Journal of Climatology, 2007)
There is now a large published literature on the strengths and weaknesses of downscaling methods for different climatic variables, in different regions and seasons. However, little attention is given to the choice of downscaling method when examining the impacts of climate change on hydrological systems. This review paper assesses the current downscaling literature, examining new developments in the downscaling field specifically for hydrological impacts. Sections focus on the downscaling concept; new methods; comparative methodological studies; the modelling of extremes; and the application to hydrological impacts. Consideration is then given to new developments in climate scenario construction which may offer the most potential for advancement within the ‘downscaling for hydrological impacts’ community, such as probabilistic modelling, pattern scaling and downscaling of multiple variables and suggests ways that they can be merged with downscaling techniques in a probabilistic climate change scenario framework to assess the uncertainties associated with future projections. Within hydrological impact studies there is still little consideration given to applied research; how the results can be best used to enable stakeholders and managers to make informed, robust decisions on adaptation and mitigation strategies in the face of many uncertainties about the future. It is suggested that there is a need for a move away from comparison studies into the provision of decision‐making tools for planning and management that are robust to future uncertainties; with examination and understanding of uncertainties within the modelling system. Copyright © 2007 Royal Meteorological Society

Changes in European drought characteristics projected by the PRUDENCE regional climate models - S. Blenkinsop; H. J. Fowler (International Journal of Climatology, 2007)
One of the key features of global climate change will be perturbations to the hydrological regime across Europe. To date, assessments of the impacts of future change have generally used results from only one climate model, thus underestimating the range of possible change projected by different climate models. Here, the skill of six regional climate models (RCMs) in reproducing the mean precipitation for the 1961–1990 period for six catchments across Europe is compared and their projections of changes in future precipitation are assessed. A simple drought index based on monthly precipitation anomalies is also described and used to assess the models. Considerable variation in model skill in reproducing monthly mean precipitation and drought statistics is observed, with model errors in the reproduction of drought events independent of those for the mean, suggesting that the models have difficulties in reproducing the observed persistence of low monthly rainfall totals. In broad terms, the models indicate decreases in summer and increases in winter precipitation across Europe. On the regional scales required for impacts analysis, considerable model uncertainty is demonstrated for future projections, particularly for drought frequency. Although increases in the frequency of long‐duration droughts are identified for catchments in southern Europe, the magnitude of this change is not certain. In contrast, for a catchment in northern England, such events are likely to become less frequent. For shorter‐duration droughts, future changes encompass the direction of change. For stakeholders in each of the regions, these changes and uncertainties pose different challenges for the management of water resources. For the scientific community, the challenge raised is how to incorporate this uncertainty in climate change projections in a way that allows those groups to make informed decisions based on model projections. It is suggested that probabilistic scenarios for specific hydrological impacts offer considerable potential to achieve this. Copyright © 2007 Royal Meteorological Society

Evidence for multiple year classes of the giant Australian cuttlefish Sepia apama in northern Spencer Gulf, South Australia - Karina C. Hall; Anthony J. Fowler; Michael C. Geddes (Reviews in Fish Biology and Fisheries, 2007)

Reconstructing past biological invasions: niche shifts in response to invasive predators and competitors - Meg M. Eastwood; Megan J. Donahue; Amy E. Fowler (Biological Invasions, 2007)

Using regional climate model data to simulate historical and future river flows in northwest England - H. J. Fowler; C. G. Kilsby (Climatic Change, 2007)

Estimated Sand and Gravel Resources of the South Merrimack, Hillsborough County, New Hampshire, 7.5-Minute Quadrangle - David M. Sutphin; Lawrence J. Drew; Brian K. Fowler (Natural Resources Research, 2007)

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Differences in kelp morphology between wave sheltered and exposed localities: morphologically plastic or fixed traits? - Meegan J. Fowler-Walker; Thomas Wernberg; Sean D. Connell (Marine Biology, 2006)

Enterococcal prosthetic valve infective endocarditis: report of 45 episodes from the International Collaboration on Endocarditis-merged database - D. J. Anderson; L. Olaison; J. R. McDonald; J. M. Miro; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; E. Abrutyn; G. Habib; S. Eykyn; P. A. Pappas; V. G. Fowler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Variation at local scales need not impede tests for broader scale patterns - Meegan J. Fowler-Walker; Sean D. Connell; Bronwyn M. Gillanders (Marine Biology, 2005)

Use of Radiotracer Techniques to Study Subcellular Distribution of Metals and Radionuclides in Bivalves from the Noumea Lagoon, New Calendonia - M. Metian; L. Hédouin; C. Barbot; J.-L. Teyssié; S. W. Fowler; F. Goudard; P. Bustamante; J.-P. Durand; J. Piéri; M. Warnau (Bulletin of Environmental Contamination and Toxicology, 2005)

Evaluation of an FRDA–EGFP genomic reporter assay in transgenic mice - Joseph P. Sarsero; Timothy P. Holloway; Lingli Li; Samuel McLenachan; Kerry J. Fowler; Ivan Bertoncello; Lucille Voullaire; Sophie Gazeas; Panos A. Ioannou (Mammalian Genome, 2005)

Effects of combined lamotrigine and valproate on basal and stimulated extracellular amino acids and monoamines in the hippocampus of freely moving rats - Shagufta Ahmad; Leslie J. Fowler; Peter S. Whitton (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Human BAC-mediated rescue of the Friedreich ataxia knockout mutation in transgenic mice - Joseph P. Sarsero; Lingli Li; Timothy P. Holloway; Lucille Voullaire; Sophie Gazeas; Kerry J. Fowler; Denise M. Kirby; David R. Thorburn; Adam Galle; Surindar Cheema; Michel Koenig; Robert Williamson; et al. (Mammalian Genome, 2004)

Arabidopsis Transcriptional Activators CBF1, CBF2, and CBF3 have Matching Functional Activities - Sarah J. Gilmour; Sarah G. Fowler; Michael F. Thomashow (Plant Molecular Biology, 2004)

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

Effects of water-soluble cigarette smoke extracts upon the release of ?-hexosaminidase from RBL-2H3 basophilic leukaemia cells in response to substance P, compound 48/80, concanavalin A and antigen stimulation - C. J. Fowler; M. Sandberg; G. Tiger (Inflammation Research, 2003)

A regional frequency analysis of United Kingdom extreme rainfall from 1961 to 2000 - H. J. Fowler; C. G. Kilsby (International Journal of Climatology, 2003)
Multi‐day rainfall events are an important cause of recent severe flooding in the UK, and any change in the magnitude of such events may have severe impacts upon urban structures such as dams, urban drainage systems and flood defences and cause failures to occur. Regional pooling of 1‐, 2‐, 5‐ and 10‐day annual maxima for 1961 to 2000 from 204 sites across the UK is used in a standard regional frequency analysis to produce generalized extreme value growth curves for long return‐period rainfall events for each of nine defined climatological regions. Temporal changes in 1‐, 2‐, 5‐ and 10‐day annual maxima are examined with L‐moments using both a 10 year moving window and the fixed decades of 1961–70, 1971–80, 1981–90 and 1991–2000. A bootstrap technique is then used to assess uncertainty in the fitted decadal growth curves and to identify significant trends in both distribution parameters and quantile estimates. There has been a two‐part change in extreme rainfall event occurrence across the UK from 1961 to 2000. Little change is observed at 1 and 2 days duration, but significant decadal‐level changes are seen in 5‐ and 10‐day events in many regions. In the south of the UK, growth curves have flattened and 5‐ and 10‐day annual maxima have decreased during the 1990s. However, in the north, the 10‐day growth curve has steepened and annual maxima have risen during the 1990s. This is particularly evident in Scotland. The 50 year event in Scotland during 1961–90 has become an 8‐year, 11‐year and 25‐year event in the East, South and North Scotland pooling regions respectively during the 1990s. In northern England the average recurrence interval has also halved. This may have severe implications for design and planning practices in flood control. Copyright © 2003 Royal Meteorological Society

Partially functional Cenpa–GFP fusion protein causes increased chromosome missegregation and apoptosis during mouse embryogenesis - Paul Kalitsis; Kerry J. Fowler; Elizabeth Earle; Belinda Griffiths; Emily Howman; Ainsley J. Newson; K. H. Andy Choo (Chromosome Research, 2003)

AM404 and VDM 11 non-specifically inhibit C6 glioma cell proliferation at concentrations used to block the cellular accumulation of the endocannabinoid anandamide - Kent-Olov Jonsson; Anna Andersson; Stig O. P. Jacobsson; Séverine Vandevoorde; Didier M. Lambert; Christopher J. Fowler (Archives of Toxicology, 2003)

Precipitation and the North Atlantic Oscillation: a study of climatic variability in northern England - H. J. Fowler; C. G. Kilsby (International Journal of Climatology, 2002)
Variations in precipitation in Yorkshire, UK, are linked to large‐scale atmospheric circulation using the North Atlantic Oscillation (NAO) index, objective Lamb weather types, and long‐term seasonal and annual precipitation indices at seven sites. Since the 1960s, a significant decrease in summer precipitation has been observed across the region, with increasing winter precipitation at western locations since 1970. At western sites, precipitation is highly correlated to the NAO, with positive and negative winter‐NAO indices producing anomalies from the long‐term winter precipitation average of 112% and 77% respectively. The recent winter half‐year precipitation increase is concentrated in March and related to a large increase in monthly NAO and the increased occurrence of westerly weather types. The decrease in summer precipitation, however, is caused by both declining receipt from westerly weather types and their decreased occurrence. This is significantly correlated to a decreasing summer index for the NAO. The NAO, the frequency of weather types and precipitation totals are all intimately linked on an annual and monthly time scale. Strong connections between winter precipitation and the NAO may prove very important, particularly in western Yorkshire where most surface water supplies are located. If the NAO can be predicted using sea‐surface temperature, it may allow the estimation of winter reservoir replenishment in western Yorkshire a few months in advance. This may provide an important predictor of future hydrological drought episodes and facilitate forward planning and management of water resource systems located in climatologically similar regions of the UK. Copyright © 2002 Royal Meteorological Society

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Annual methane emission from Finnish mires estimated from eddy covariance campaign measurements - K. J. Hargreaves; D. Fowler; C. E. R. Pitcairn; M. Aurela (Theoretical and Applied Climatology, 2001)

Comparison of the Effects of Wet N Deposition (NH4Cl) and Dry N Deposition (NH3) on UK Moorland Species - Ian D. Leith; Lucy J. Sheppard; Carole E.R. Pitcairn; J. Neil Cape; Paul W. Hill; Valerie H. Kennedy; Y. Sim Tang; Ron I. Smith; David Fowler (Water, Air, & Soil Pollution, 2001)

Foliar Nitrogen as an Indicator of Nitrogen Deposition and Critical Loads Exceedance on a European Scale - Carole E.R. Pitcairn; Ian D. Leith; David Fowler; Ken J. Hargreaves; Masoud Moghaddam; Valerie H. Kennedy; Lennart Granat (Water, Air, & Soil Pollution, 2001)

Measurements of Ozone Deposition to Vegetation Quantifying the Flux, the Stomatal and Non-Stomatal Components - David Fowler; Chris Flechard; J. Neil Cape; Robert L. Storeton-West; Mhairi Coyle (Water, Air, & Soil Pollution, 2001)

Effects of staurosporine, U-73122, wortmannin, 4-hydroxynonenal and sodium azide upon the release of secreted β-amyloid precursor protein from human platelets in response to thrombin stimulation - Henrietta L.M. Hedin; Lisa Nilsson; Christopher J. Fowler (Molecular and Cellular Biochemistry, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Oxidation of atmospheric methane in Northern European soils, comparison with other ecosystems, and uncertainties in the global terrestrial sink - K. A. Smith; K. E. Dobbie; B. C. Ball; L. R. Bakken; B. K. Sitaula; S. Hansen; R. Brumme; W. Borken; S. Christensen; A. Priemé; D. Fowler; J. A. Macdonald; et al. (Global Change Biology, 2000)
Summary This paper reports the range and statistical distribution of oxidation rates of atmospheric CH 4 in soils found in Northern Europe in an international study, and compares them with published data for various other ecosystems. It reassesses the size, and the uncertainty in, the global terrestrial CH 4 sink, and examines the effect of land‐use change and other factors on the oxidation rate. Only soils with a very high water table were sources of CH 4 ; all others were sinks. Oxidation rates varied from 1 to nearly 200 μg CH 4 m −2 h −1 ; annual rates for sites measured for ≥1 y were 0.1–9.1 kg CH 4 ha −1 y −1 , with a log‐normal distribution (log‐mean ≈ 1.6 kg CH 4 ha −1 y −1 ). Conversion of natural soils to agriculture reduced oxidation rates by two‐thirds –‐ closely similar to results reported for other regions. N inputs also decreased oxidation rates. Full recovery of rates after these disturbances takes > 100 y. Soil bulk density, water content and gas diffusivity had major impacts on oxidation rates. Trends were similar to those derived from other published work. Increasing acidity reduced oxidation, partially but not wholly explained by poor diffusion through litter layers which did not themselves contribute to the oxidation. The effect of temperature was small, attributed to substrate limitation and low atmospheric concentration. Analysis of all available data for CH 4 oxidation rates in situ showed similar log‐normal distributions to those obtained for our results, with generally little difference between different natural ecosystems, or between short‐and longer‐term studies. The overall global terrestrial sink was estimated at 29 Tg CH 4 y −1 , close to the current IPCC assessment, but with a much wider uncertainty range (7 to > 100 Tg CH 4 y −1 ). Little or no information is available for many major ecosystems; these should receive high priority in future research.

Neurotoxicity of glutamate in chick telencephalon neurons: reduction of toxicity by preincubation with carbachol, but not by the endogenous fatty acid amides anandamide and palmitoylethanolamide - Mikael Andersson; Stig O. P. Jacobsson; Kent-Olov Jonsson; Gunnar Tiger; Christopher J. Fowler (Archives of Toxicology, 2000)

Behavioral tolerance to the force differentiation effects of diazepam and midazolam in rats - S. E. Bowen; S. C. Fowler; J. A. Stanford; M. J. Kallman (Psychopharmacology, 2000)

CHARACTERIZATION OF JOK-1, A HUMAN GASTRIC EPITHELIAL CELL LINE - N. OKAYAMA; M. R. FOWLER; S. R. JENNINGS; P. PATEL; R. SPECIAN; B. ALEXANDER; T. H. JACKSON; T. OSHIMA; K. SHANNON; J. S. ALEXANDER (In Vitro Cellular & Developmental Biology - Animal, 2000)

The effect of termite biomass and anthropogenic disturbance on the CH 4 budgets of tropical forests in Cameroon and Borneo - J. A. Macdonald; D. Jeeva; P. Eggleton; R. Davies; D. E. Bignell; D. Fowler; J. Lawton; M. Maryati (Global Change Biology, 1999)
Summary The exchange of CH 4 between tropical forests and the atmosphere was determined by simultaneously measuring the net CH 4 flux at the soil surface and assessing the flux contribution from soil‐feeding termite biomass, both within the soil profile and in mounds. In Cameroon the flux of CH 4 ranged from a net emission of 40.7 ng m –2 s –1 to a net CH 4 oxidation of –53.0 ng m –2 s –1 . Soil‐inhabiting termite biomass was significantly correlated with CH 4 flux. Termite mounds emitted up to 2000 ng s –1 mound –1 . Termite‐derived CH 4 emission reduced the soil sink strength by up to 28%. Disturbance also had a strong effect on the soil sink strength, with the average rate of CH 4 oxidation, at – 17.5 ng m –2 s –1 , being significantly smaller (≈ 36%) at the secondary forest site than the –27.2 ng m –2 s –1 , observed at the primary forest site. CH 4 budgets calculated for each site indicated that both forests were net sinks for CH 4 at – 6.1 kg ha –1 y –1 in the near‐primary forest and – 3.1 kg ha –1 y –1 in the secondary forest. In Borneo, three forest sites representing a disturbance gradient were examined. CH 4 oxidation rates ranged from 0 to – 32.1 ng m –2 s –1 and a significant correlation between the net flux and termite biomass was observed only in an undisturbed primary forest, although the biomass was insufficient to cause net emission of CH 4 . Rates of CH 4 oxidation were not significantly different across the disturbance gradient but were, however, larger in the primary forest (averaging – 15.4 ng m –2 s –1 ) than in an old‐growth secondary forest (–13.9 ng m –2 s –1 ) and a young secondary re‐growth (– 10.8 ng m –2 s –1 ). CH 4 flux from termite mounds ranged from net oxidation in an abandoned mound to a maximum emission of 468 ng s –1 mound –1 . CH 4 budgets calculated for each site indicated that CH 4 flux from termite mounds had an insignificant effect on the budget of CH 4 at the regional scale at all three forest sites. Annual oxidation rates were – 4.8, – 4.2 and – 3.4 kg ha –1 y –1 in the primary, secondary and young secondary forests, respectively.

The Global Exposure of Forests to Air Pollutants - David Fowler; J. Neil Cape; Mhairi Coyle; Chris Flechard; Johan Kuylenstierna; Kevin Hicks; Dick Derwent; Colin Johnson; David Stevenson (Water, Air, & Soil Pollution, 1999)

Minimal requirements for in vitro reconstitution of the structural subunit of light-harvesting complexes of photosynthetic bacteria - John B. Todd; Paul A. Recchia; Pamela S. Parkes-Loach; John D. Olsen; Gregory J. S. Fowler; Peter McGlynn; C. Neil Hunter; Paul A. Loach (Photosynthesis Research, 1999)

Dopamine-transporter occupancy after intravenous doses of cocaine and methylphenidate in mice and humans - S. J. Gatley; Nora D. Volkow; Andrew N. Gifford; Joanna S. Fowler; Stephen L. Dewey; Yu-Shin Ding; Jean Logan (Psychopharmacology, 1999)

Age structure and diel activity of pouting on the Poole Bay artificial reef - A. J. Fowler; A. C. Jensen; K. J. Collins; I. P. Smith (Journal of Fish Biology, 1999)
Predominantly (86·6%) juvenile ( Trisopterus luscus formed inactive, nonfeeding schools around artificial reef units in Poole Bay, Dorset, during daylight hours and the position of the schools was related to differing tidal conditions. At current speeds >0·3 m s −1 , the pouting congregated close to the reef units, remained low in the water column and maintained position. At current speeds −1 , the schools were more dispersed, further away from reef units and higher in the water column. This tidally‐related behaviour is thought to be related to energy conservation during the daylight hours, when the pouting utilize the lee of reef units during strong tidal currents. Between 15 and 30 min after dusk the majority of pouting left the artificial reef, and returned 45–60 min before dawn. A brief mark‐recapture programme, using 0‐ to 1‐group pouting, confirmed that a proportion of the pouting tagged were present on the artificial reef up to 5 days after marking, suggesting that the site was being used to some extent as a home reef. The nocturnal foraging pattern may be related to the availability of prey species.

Deposition Monitoring in Europe - J. W. Erisman; M. G. Mennen; D. Fowler; C. R. Flechard; G. Spindler; A. Grüner; J. H. Duyzer; W. Ruigrok; G. P. Wyers (Environmental Monitoring and Assessment, 1998)

Validation of age determination from otoliths of the King George whiting Sillaginodes punctata (Perciformes) - A. J. Fowler; D. A. Short (Marine Biology, 1998)

Chiral drugs: comparison of the pharmacokinetics of [ 11 C] d-threo and l-threo -methylphenidate in the human and baboon brain - Y.-S. Ding; J. S. Fowler; N. D. Volkow; S. L. Dewey; G.-J. Wang; J. Logan; S. J. Gatley; N. Pappas (Psychopharmacology, 1997)

Subchronic effects of clozapine and haloperidol on rats' forelimb force and duration during a press-while-licking task - J. A. Stanford; Stephen C. Fowler (Psychopharmacology, 1997)

Integration of trinucleotide microsatellites into a linkage map of Citrus - J. M. H. Kijas; M. R. Thomas; J. C. S. Fowler; M. L. Roose (Theoretical and Applied Genetics, 1997)

Non-neutralizing monoclonal antibodies to a trypsin-sensitive site on the major glycoprotein of rotavirus which discriminate between virus serotypes - Barbara S. Coulson; K. J. Fowler; J. R. White; R. G. H. Cotton (Archives of Virology, 1987)

Towards a phylogeny of phototrophic purple sulfur bacteria?16S rRNA oligonucleotide cataloguing of 11 species of Chromatiaceae - Valerie J. Fowler; Norbert Pfennig; Wolfgang Schubert; Erko Stackebrandt (Archives of Microbiology, 1984)

Towards a phylogeny of phototrophic purple sulfur bacteria ? the genus Ectothiorhodospira - Erko Stackebrandt; Valerie J. Fowler; Wolfgang Schubert; Johannes F. Imhoff (Archives of Microbiology, 1984)

The relatedness of Prochloron sp. Isolated from different didemnid ascidian hosts - Erko Stackebrandt; Elke Seewaldt; Valerie J. Fowler; Karl-Heinz Schleifer (Archives of Microbiology, 1982)

General and renal toxicity of phenacetin, paracetamol and some anti-mitotic agents in the rat - G. Peters; Nicole Baechtold-Fowler; J. Ph. Bonjour; Franoise Chomty-Dizi; Bernadette Filloux; R. Guidoux; J. P. Guignard; Lise Peters-Haefeli; Franoise Roch-Ramel; J. L. Schelling; Chr. Hedinger; Erika Weber (Archives of Toxicology, 1972)

Sectional notes - Cecil W. Frutchey; W. B. Ward; Marx Koehnke; J. C. Campbell; H. J. Evans; Earl B. Tussing; O. D. Burke; John Noonan; M. R. Harris; Wm. A. Riedl; W. A. Fowler (American Journal of Potato Research, 1947)